Developing radio frequency technology for enhancing the processing characteristics of gluten-free rice dough based on gelatinization degree - Dongsheng Hu; Yingqi Tian; Jiahong Yuan; Mengge Li; Rui Li; Shaojin Wang (Journal of Food Engineering, 2026)

Quality formation mechanism of shiitake mushrooms during multiphase microwave drying (MMD) - Zhenbin Liu; Jia Luo; Jiayi Zhang; Rui Weng; Wenchao Liu; Hongbo Li; Huan Cheng; Dong Wang; Hengchao E; Lu Tian; Haizhen Mo; Liangbin Hu (Food Control, 2026)

Efficient sludge reduction and phosphorus recovery in innovative coupled sequencing batch and worm reactor Process: Performance, mass balance and metagenomic mechanisms - Jingjing Zhang; Lipin Li; Xuanhe Yang; Siqi Chen; Zhe Li; Rui Li; Chunlei Wang; Yu Tian (Bioresource Technology, 2026)

Pathogenic mechanisms of Trichoderma hamatum, a postharvest pathogen causing fruit rot - Hai-Rui Wang; Xiong Xiong; Wen-Chao Li; Shuang-Jiao Ma; Yan-Xue Liu; Tong Liu; Ke-Xiang Gao; Chuan-Rong Li; Hui-Xiang Liu; Ye-Han Tian (Postharvest Biology and Technology, 2026)

Silica‑calcium composite amendments increase the erosion resistance of soda saline-alkali soils under consecutive extreme rainfall events - Zhuo Tian; Dongli She; Weidong Liang; Hongde Wang; Rui Fu; Shuo Wang; Yinhao Bai (CATENA, 2026)

Organic amendment quality and quantity govern microbial necromass contributions to soil carbon sequestration: a meta-analysis - Jiaqi Hao; Mengdi Wang; Yiting Chen; Hui Xia; Hailin Zhang; Pete Smith; Yapeng Jiao; Binbin Cao; Yan Gao; Jianglan Shi; Xiangtian Meng; Rui Yin; et al. (Soil Biology and Biochemistry, 2026)

Using spherical protrusions for simultaneous pressure pulsation mitigation and efficiency enhancement in a giant Francis turbine across a wide load operation - Lei Tang; Xiao-Wen Huang; Rui Zhao; Tian-Yi Shi; Wen-Quan Wang (Ocean Engineering, 2026)

One-step hydrophilic network for simultaneous boost in scaling prone cation removal and resistance to organic fouling of nanofiltration membranes - Rui Yu; Haonan Zhang; Yanqi Gan; Xupan Wang; Tian Wang; Jiahe Li; Mengqi Shi; Chenxi Dong; Feng Wu (Journal of Environmental Chemical Engineering, 2026)

Rapid inverse design of double-curved beams for multi-stable metamaterials based on prescribed deformation histories through artificial neural network - Chun-Zheng Zhao; Xin Wang; Rui Zhang; Yongfeng Jiang; Haibo Ji; Zhen Li; Bingyang Li; Pengfei Wang; Feng Jin; Tian Jian Lu (Engineering Structures, 2026)

Mechanistic insights into the adsorption and separation of nonpolar molecules on delocalization porous carbon: Dispersion interactions enhanced by multiple bonds - Peixin Wang; Jingxu Tian; Da Wei; Yue Sun; Bo Liu; Wenji Pi; Jun Ma; Yunfeng Zhang; Hongyu Chen; Rui Shi; Yang Guo; Xiang Xu; et al. (Chemical Engineering Journal, 2026)

Spirofluorene-grafted triazine branched poly(aryl piperidinium) anion exchange membranes for high performance water electrolysis and flow batteries - Wei-Feng Yang; Yong-Xin An; Rui Guo; Han Yan; Tian-Tian Wang; Chang-Ping Liu; Yong-Mei Tian; Wen-Bin Sun (Chemical Engineering Journal, 2026)

A review of atmospheric black carbon research progress in China - Qi Zhou; Shunyao Wang; Shujun Bie; Junjie Cai; Yingjun Chen; Yuan Cheng; Xiang Ding; Jianwei Gu; Jie Li; Weijun Li; Dantong Liu; Jiaying Liu; et al. (Atmospheric Environment, 2026)

Study on upper bound solution of anti-overturning bearing capacity of pile-bucket composite foundation in sand - Guang-si Chen; Rui Zhou; Le Wang; Run Liu; Tian-liang Li (Marine Georesources & Geotechnology, 2026)

Kosakonia oryziphila KC516 mediated growth promotion of Cosmos bipinnatus in phosphogypsum by modulating rhizosphere geochemistry and root transcriptome - Jing Zhang; Hao-Tian Dong; Yuan-Chun Yang; Rui Liu; Shuai Wang; Ao-Li Zhang; Yuan Su; Ming-Hua Dong; Yan-Ru Cao; Hua-Li Zhang (Environmental Geochemistry and Health, 2026)

Prevalence and risk factors of bovine tuberculosis in dairy cattle, 2020–2025: A systematic review and meta-analysis of available literature - Qi Wang; Xiao-Nan Wang; Xiao-Qun Liu; Long-Ge Zhao; Zi-Tong Jing; Tian Tian; Jia-Ting Zhang; Yi-Xing Zhao; Jian-Ming Li; Nai-Chao Diao; Kun Shi; Rui Du (Preventive Veterinary Medicine, 2026)

LhCAT2-mediated crosstalk between reactive oxygen species homeostasis and anthocyanin biosynthesis enhances zinc tolerance in Liriodendron hybrid - Yongchao Ke; Yu Liu; Teja Manda; Tian Min; Rui Wang; Wenbin Su; Liming Yang (Journal of Hazardous Materials, 2026)

Metal covalent organic frameworks with donor-acceptor-catalytic site (D-A-C) for boosting CO2 photoreduction - Shi-Wen Zhang; Wen-Yi Zheng; Shu-Zhi Hu; Qian-Rui Mao; Mi Tian; Wang-Kang Han; Zhi-Guo Gu (Chemical Engineering Journal, 2026)

Entropy-driven engineering in AFe2O4 spinel enabling broadband microwave absorption - Xinglai Yuan; Wei Li; Qiancheng Gao; Fan Zhang; Ye Yuan; Xiaohan Wang; Yanqiu Zhu; Mi Tian; Hailong Wang; Rui Zhang; Biao Zhao; Qinghu Wang; et al. (Chemical Engineering Journal, 2026)

Polymer-based hydrogen barrier coatings: Material design, mechanisms, and theoretical simulation - Zhuofan Li; Zhibin Chen; Lingwei Ma; Jinke Wang; Xin Guo; Rui Tian; Bowei Zhang; Huaiyuan Wang; Dawei Zhang (Chemical Engineering Journal, 2026)

Unraveling the spatial paradox of multi-hazard mitigation: divergent impacts of urban form and function on heat and pluvial flood hazards - Bomeng Wu; Rui Sun; Zhaoren Wang; Ye Tian; Lanyu Qin; Hezi Bai; Mengyuan Chen; Huocheng Lin; Shuang Li; Shuanning Zheng (Natural Hazards, 2026)

Different drivers of active and inert carbon fraction on forest soil aggregate stability: a functional partitioning approach - Jing Lin; Rui Wang; Miao Xia; Jian-cong Zhang; Peng Qiu; Ke-xin Zhang; Bo Chang; Yu-lin Zhang; Tian-zi Xie; Yi Jian; Jia-yuan Wang; Shan-shan Guo (Journal of Soils and Sediments, 2026)

Field‐Deployable RPA ‐ CRISPR /Cas12a Detection of Decapod Iridescent Virus 1 in Shrimp - Rui Wang; Yanfeng Wang; Lihan Wang; Yishuai Du; Huiqin Tian; Tianlong Qiu; Liang Chi (Journal of Fish Diseases, 2026)
Decapod iridovirus 1 (DIV1) is a highly lethal pathogen that infects decapod crustaceans including Litopenaeus vannamei , causing mass mortality in cultured shrimp and severe economic losses worldwide. The ATPase gene is a highly conserved region within the DIV1 genome, plays a critical role in viral replication and represents an ideal target for molecular diagnostic development. In this study, we established a rapid, sensitive and field‐adaptable detection platform for DIV1 by integrating recombinase polymerase amplification (RPA) with the CRISPR/Cas12a system. RPA enables efficient isothermal amplification of target nucleic acids, achieving exponential enrichment of the target nucleic acids and exerting the function of signal amplification. While the CRISPR/Cas12a system upon crRNA‐guided specific recognition of the amplicon, triggers robust trans‐cleavage activity against reporter probes for signal generation and readout. After systematic optimization, the RPA reaction was performed at 38°C for 10 min and the CRISPR‐Cas12a reaction was conducted at 37°C for 20 min. The integrated two‐step workflow completed detection within 40 min, with a limit of detection of 2.3 × 10 1 copies/μL. Specificity evaluation confirmed that the RPA‐CRISPR/Cas12a assay exclusively recognised DIV1 without cross‐reaction with other major shrimp pathogens. Further validation using clinical shrimp samples demonstrated stable and reliable performance, supporting its practical utility in aquaculture settings. In conclusion, the established CRISPR/Cas12a‐based detection platform provides a robust technical tool for early warning and on‐site rapid screening of DIV1, facilitating timely disease control and risk management in shrimp farming.

AGR2-high cells drive a FOXM1-mediated pro-malignancy program in non-functional pancreatic neuroendocrine tumors (NF-PanNETs) and informatively predict patient outcomes - Junya Peng; Rui Jiang; Jiajuan Tu; Wanli Liu; Lu Ping; Ruikang Dun; Wenyu Zhang; Hao Chen; Yihong Shi; Xu Pan; Panpan Jia; Mengjie Li; et al. (Science Bulletin, 2026)

Compartment-specific host association and mobility shape ARG risk in aquaculture systems - Zhong-Quan Jiang; Rui-Kai Xing; Di Peng; Yuan-Hao Ren; Tian-Yi Wei; Wen-Bo Guo; Zhe-Min Shen; Chao-Nan Wang; Feng-Li Zhang; Tao Yuan (Journal of Hazardous Materials, 2026)

Effective photodynamic inactivation of curcumin in combination with ethylenediaminetetraacetic acid against Burkholderia gladioli pathovar cocovenenans - Xiu-Xia Tian; Jia-Jun Yan; Rui Huang; Quan Zhou; Qi-Ying Zeng; Yu-Ming Jiang; Zi-Hui Chen; Hai-Yan Wang; Bai-Sheng Li; Yong-Ning Wu; Wei-Liang Wu (Food Research International, 2026)

Identification of distributed heat sources intensities with deterministic flow fields in ventilated spaces - Yemin Liu; Xiaoliang Shao; Rui Wang; Xiaohe Tian; Huifang Fan; Jianeng Cui (Building and Environment, 2026)

Calculation of hydrogeological parameters based on a high-flow long-duration water release test of multiple deep boreholes, Xiadian coalfield, North China - Fang Li; Rui Luo; Zhijia Yu; Wubin Gao; Jianggen He; Yu Ping; Shiyuan Tian; Zihan Wang; Tao Cheng; Colin G. Farquharson; Xinyi Wang (Hydrogeology Journal, 2026)

How does climate risk affect the grain production resilience: an analysis of mechanism pathways and mitigation strategies - Xiaohan Pei; Jintao Wang; Tian Qi; Rui Shi; Wenxin Liu; Minjuan Zhao (Climatic Change, 2026)

Prevotella copri impairs bone mass via osteoclast activation in mice - Rui Li; Haiyan Zhang; Shiyong Xin; Tiantian Zeng; Wenchu Qian; Yawen Sun; Yunfei Cao; Yuxin Wang; Bin Li; Ming Tian; Hai Lin; Haifang Li (Molecular and Cellular Biochemistry, 2026)

Hierarchical Studies in TRAP2 Mice Demonstrate that Neuronal Activation and Mitochondrial Networks Integration Constitute the Key Mechanism Underlying Painful Syncope - Xueyin Pu; Yulu Xia; Ziwei Ni; Changlei Zhu; Kunlong Zhang; Bozhi Liu; Rui Lin; Jingxuan Zhu; Hui Liu; Shujiao Li; Yunqiang Huang; Feifei Wu; et al. (Neuroscience Bulletin, 2026)

A nationwide analysis of hospitalised patients with lower respiratory infections in China: life-stage-specific pathogen spectra, co-detection networks, and sex disparities - Yamin Sun; Min Wang; Tian Qin; Jue Liu; Jiale Yuan; Pei Li; Xinchang Lun; Zhigang Wang; Linghang Wang; Rui Song; Xi Wang; Ronghua Jin; et al. (Science Bulletin, 2026)

Amelioration of obesity-induced endothelial dysfunction by a synthetic ocean-derived peptide via regulating PPARα/γ pathway - Tiantian Zhou; Xinyi Chen; Yuehan Wang; Xutao Zhang; Lingchao Miao; Rui Tian; Yumeng Li; Yingying Feng; Xin Wu; Wai San Cheang (Food Research International, 2026)

A proton-relay strategy with K-modulated N/P proton pairs over Ru-based catalysts for efficient ammonia decomposition - Shuyu Chen; Rui Chen; Liang Wang; Haibo Tang; Rui Wang; Tian Tian; Yawei Zhou; Zihan Meng; Haolin Tang (Chemical Engineering Journal, 2026)

Spatial and environmental niche differentiation facilitates sympatric macaques' coexistence in montane-canyon landscapes: Implications for conservation - Wei Zhou; Yuan Wang; Deyan Ge; Qisen Yang; Gang Song; Jilong Cheng; Tian Tian; Yu Zhang; Jinbo Xu; Ying Liu; Weibo Wang; Xiaochuan Wang; et al. (Biological Conservation, 2026)

Genome-wide association analysis and candidate gene identification for plant height in Shanxi local foxtail millet varieties - Wei Zhou; Huibin Qin; Haigang Wang; Hui Zhi; Rui Huang; Sen Hou; Junjie Wang; Ling Chen; Xiang Tian; Zhijun Qiao; Zhixin Mu; Xianmin Diao (Theoretical and Applied Genetics, 2026)

Molecular characterization of a novel partitivirus isolated from Fusarium solani, the causal agent of tobacco root rot - Xiao Wu; Ying Wang; Rui Guo; Ya Rong Wang; Si Jun Li; Xiang Ping Zhou; Jie Zhong; Yan Song Xiao; Tian Bo Liu (Archives of Virology, 2026)

SYVN1-provoked RASA1 ubiquitination promotes pulmonary inflammation in chronic obstructive pulmonary disease - Ju-Hong Wu; Yi-Cheng Ma; Yu-Qi Wang; Hai-Long Miao; Meng-Xue Liu; Dong-Xu Hua; Min-Min Tang; Tian-Rui Sui; Zhi-Yong Wu; Yu Wang; Jin Yang; Hui Zhao; et al. (Inflammation Research, 2026)

Selective separation of naphthalene sulfonic acids and salts from wastewater by electric field-assisted nanofiltration membranes - Yaning Tian; Jiansuxuan Chen; Rui Gao; Ruobin Dai; Zhiwei Wang (Water Research, 2026)

Dexmedetomidine regulates fatty acid oxidation through the AMPK/PGC-1α/CPT1A pathway to mitigate renal ischaemia-reperfusion injury - Cong-Li Zhang; Yan Yan; Ke Wang; Jun-Jie Ma; Wen-Jun Xu; Gang Liu; Xing-Chun Zhu; Zhi-Gao Zhu; Hao-Feng Ding; Zi-Rui Ke; Kai Yao; Fang-Tian Fan; et al. (Toxicology and Applied Pharmacology, 2026)

Ascosphaera apis invasion alters the expression pattern, alternative splicing and alternative polyadenylation of transcripts in the eastern honeybee larval gut - Jianfeng Qiu; Fangji Wang; Xiang Li; Tao Wu; Xin Jing; Zhenzhen Zuo; Jing Tian; Dafu Chen; Rui Guo (Journal of Invertebrate Pathology, 2026)

Dual-encapsulated γ-cyclodextrin liposomal hydrogel beads crosslinked with Ca2+-SHP for pH-responsive and targeted lutein delivery - Lanxin Zhang; Shengnan Wang; Xuejing Tian; Rui Wang; He Liu (Journal of Food Engineering, 2026)

Anti-adhesion nanofiltration membranes via a fluorine-rich microenvironment for broad-Spectrum micropollutant removal - Yanqi Gan; Rui Yu; Xupan Wang; Tian Wang; Jiahe Li; Feng Wu; Mengqi Shi (Chemical Engineering Journal, 2026)

Natural longevity modulator: aging modulatory effects of Eurycoma longifolia Jack polysaccharides in C. elegans and D. melanogaster - Yan Liu; Hailing Wang; Rui Wu; Yuan Tian; Xin Meng (Biogerontology, 2026)

Effect of two double-stranded RNA viruses on the virulence of the phytopathogenic fungus Fusarium oxysporum - Jing Wang; Yunxia Ni; Xintao Liu; Hui Zhao; Xingbei Zhao; Rui Qiu; Siyuan Feng; Xiaoyuan Tian; Shouye Song; Shujun Li; Hongyan Liu (Archives of Virology, 2026)

Muscone Exerts Rapid Antidepressant Effects Through Modulating Glutamatergic Neural Transmission in the Anterior Cingulate Cortex Against Peripheral Inflammation-induced Depression - Xiaoyun Qiu; Xiaojie Zhang; Yuanzhi Yang; Minjuan Sun; Xiaoli Da; Jiaying Liu; Rui Wang; Jingjia Liang; Xuhong Jiang; Gang Tian; Qiyuan Shan; Yu Du; et al. (Neuroscience Bulletin, 2026)

Remote sensing-based estimation of global litterfall dynamics in forest ecosystems and its potential impact on soil respiration - Chunsheng Wang; Qingjiu Tian; Wenmin Zhang; Lili Chang; Jia Tian; Rui Zhang (Remote Sensing of Environment, 2026)

Valorization of industrial carbide slag via microwave processing: A low-cost route to high-performance CaO-based CO2 sorbents - Fang Wang; Yi Dong; Shaojun Luo; Zixia Tian; Shuo Cui; Rui Cao; Zibin Pan; Ping Ning; Futing Xia; Jiayu Feng; Lijuan Jia (Journal of Environmental Management, 2026)

Unraveling the mechanism of improved gas cell structure in rice bread by radio-frequency-controlled gelatinization degree: A focus on protein-starch matrix and dough liquor interface - Dongsheng Hu; Yingqi Tian; Qianjie Xiong; Mengge Li; Rui Li; Shaojin Wang (Food Research International, 2026)

Highly crystalline poly(heptazine imide) with improved intra- and inter-plane charge transport for efficient photocatalytic degradation of gaseous acetaldehyde - Dongying Wang; Lei Zhang; Rui Tian; Junjie Xu; Shuhao Sun; Beibei Cai; Ruijie Sun; Fei He (Chemical Engineering Journal, 2026)

Bioaerosol emission in public washroom under different time intervals of working day and critical exposure time for sanitary workers - Wajid Ali; Zi-qi Yang; Chun-shu Tian; Rui-wen Li; Xu Zhang; Qing Yan; Ke-yu Chen; Si-bo Cheng; Rong-xin Wang; Cheng Yan (Building and Environment, 2026)

Integrated Transcriptomics and Machine Learning Reveal Lipid Metabolism Related Genes in Ischemic Stroke - Qiu-Lin Wang; Chang-Le Fang; Tian-Hao Bao; Rui-Ze Niu (Journal of Molecular Neuroscience, 2026)

Conjugated organic polymer enables external-sacrificial-agent-free photocatalytic uranium extraction with efficiency boosted by oxygen pre-activation - Xuefeng Tian; Jipeng Li; Xuewen Cao; Jiacheng Zhang; Rui Huang; Peng Lin; Ning Wang; Yihui Yuan (Science Bulletin, 2026)

Multifaceted environmental footprints of spent coffee grounds valorization: from waste management to fuel and material production - Shuying Huang; Lan Wang; Jingwen Wang; Xi Tian; Mei Li; Xinyi Zhang; Dungang Gu; Tingting Hu; Rui Liu; Guanghui Li; Jiaqi Lu (Resources, Conservation and Recycling, 2026)

Algal ecological dynamics tracking model for studying hydrodynamic impacts on algae transport and accumulation in a shallow lake - Fei Du; Xiaobo Liu; Shiyan Wang; Chang Liu; Aiping Huang; Weijie Wang; Budong Li; Rui Gao; Xin Tian; Zhen Han; Hao Fan; Bi Wu (Journal of Hydrology, 2026)

A Cu-based catalytic molecularly imprinted electrochemical sensor on paper for phthalylsulfacetamide detection in environmental water - Shuyan Miao; Jing Zhou; Zhen Xu; Yuting Wang; Rui Liu; Tian Gan (Journal of Environmental Chemical Engineering, 2026)

Triple-synergistic nanotherapeutics for acute and chronic colitis management via programmable multidimensional modulation - Penghui Wang; Yue Zhao; Ning Tian; Xiangling Liu; Tenghui Tian; Difu Zhu; Fangbing Liu; Hengyan Liu; Ling Li; Zhiyu Ren; Deok Chun Yang; Lei Zhao; et al. (Chemical Engineering Journal, 2026)

Dynamic electric field modulation via BaTiO3-based staggered-type heterojunction for all-solid-state lithium-sulfur batteries - Yancheng Yang; Sizhe Wang; Fei Liang; Haizhou Zhao; Yi Gu; Rujing Liu; Jian Sun; Yao Yao; Rui Tian; Haojie Song (Chemical Engineering Journal, 2026)

Curcumin-derived smart anti-corrosion coating for early damage warning and active protection in diverse lighting and corrosive environments - Jinke Wang; Xin Guo; Congshu Huang; Danni Shang; Zhibin Chen; Rui Tian; Lingwei Ma; Dawei Zhang (Chemical Engineering Journal, 2026)

Experimental and numerical analysis of supply air jet in stratum ventilation for cooling - Yong Cheng; Yulong Xie; Rui Wang; Teng Li; Xue Tian (Building and Environment, 2026)

Relationship between expression of derived factor-1CXC chemokine receptor 4 in tumor tissues of patients with non-small cell lung cancer and postoperative lymph node metastasis - Zhanwu Zhang; Xiaoming Wang; Rui Tian; Kunpeng Duan; Xu Zhang (Journal of Molecular Histology, 2026)

Effects of purple corn anthocyanins on feed intake, body weight, antioxidant activity, lipid metabolism, rumen fermentation, and rumen microbiota and function in perinatal goat does - Qi Lu; Yiqing Xu; Jixiao Qin; Shuanglong Xie; Rui Chen; Yiming Ban; Chengcheng Gao; Peiyao Li; Xu Wang; Xingzhou Tian (Animal Feed Science and Technology, 2026)

Qualitative analysis of chemical constituents and study on the biological activity of Polygonum perfoliatum L - Chaochen Yue; Ya Zhang; Juan Xue; Tian Lu; Lei Li; Yanjie Wang; Rui Zhou; Di Gao; Huifang Chai (Natural Product Research, 2026)

Experimental investigation on the dynamic characteristics of marine soft soil under temperature effects - Rui Rui; Yinjie Peng; Zijin Tian; Jinyuan Wang (Soil Dynamics and Earthquake Engineering, 2026)

Multi-omics reveals that Sophora alopecuroides lysine decarboxylase (SaLDC)-mediated polyamine metabolism enhances salt tolerance and early flowering in Arabidopsis - Yongli Tian; Rui Wang; Jing Su; Wenjuan Li; Ping Liu; Chengke Luo; Jiaojiao Qian; Danting Zhang; Peifu Li; Bin Wang; Rong Yang; Tianli Ma; et al. (Plant Science, 2026)

Opposite effects of R1234yf on the flammability limits of R600a refrigerant: Experimental and kinetic insight - Xueyan Wang; Shanzhu Hu; Rui Sun; Hua Tian; Gequn Shu; Zhao Yang (International Journal of Refrigeration, 2026)

Gliadin hydrolysate-chitosan bilayer nanoparticles for berberine delivery: Controlled release, enhanced antioxidant activity, and lipid digestion regulation - Xiaoxiao Li; Yi Zhao; Aimei Liao; Yinchen Hou; Xinrui Zhang; Hailong Tian; Luyang Wang; Jin Liu; Jinyang Zhang; Jihong Huang; Rui Tan (Food Chemistry, 2026)

Effect of dry-blanching pretreatment and drying using radio frequency energy on the dehydration performance, structural and quality properties of tiger nuts - Mengge Li; Yingqi Tian; Liumin Fan; Dongsheng Hu; Rui Li; Shaojin Wang (Food Control, 2026)

Imidacloprid exposure at population-relevant doses induces hepatic lipid dysregulation: Exploring the role of cGAS-STING pathway-mediated hepatocyte senescence - Yuhan Zhang; Yuqing Dai; Yihong Di; Bing Wu; Xueyan Tian; Limeng Xiong; Zeyang Bai; Jinhao Jia; Jiaming Fu; Xiaoyu Li; Yi Zhao; Hao Hu; et al. (Environmental Research, 2026)

In situ reconstruction of defect-engineered bimetallic (DA)Ni/Mo–MOFs@TiO2 generates an anion-protected active hydroxides via: Towards corrosion-resistant seawater photoelectrolysis for hydrogen production - Yue Li; Peihua Li; Rufeng Tian; Xingzi Bian; Jian Wang; Rui Li; Wanggang Zhang; Jiancheng Wang; Yiming Liu (Chemical Engineering Journal, 2026)

Nitrogen-fixing bacteria and arbuscular mycorrhizal fungi alleviated nitrogen limitation in halophytes and reduced soil salinity in salt-aggregating and salt-secreting plants - Zehao Zhang; Tian Li; Rui Hu; Zhanyong Fu; Yao Zhang; Jinzhao Ma; Ping Wang; Jingkuan Sun (Plant and Soil, 2026)

Research progress on quorum-quenching strategies for membrane biofouling control - Hongwei Wu; Kuo Yang; Yifan Gao; Rui Xu; Yuzhang Feng; Yinning Wang; Huimin Lin; Siqi Hu; Gege Tian; Jiaying Li; Pingfeng Yu; Bing Zhang (ENGINEERING Environment, 2026)

Correction to: Unveiling Differences in Source Apportionment and Optical Properties of Wintertime Carbonaceous Aerosols in Northern and Southern Chinese Cities - Rui Li; Qiyuan Wang; Jie Tian; Yong Zhang; TingTing Wu; Lu Qi; Yang Chen; Shaofei Kong; Suixin Liu; Jin Wang; Julian Shi; Yuemei Han; et al. (Aerosol Science and Engineering, 2026)

Quantifying the critical regulator role of irradiation-enhanced electric field in nanoplastics aggregation with heavy metals - Yaowu Zhang; Xianzheng Yuan; Ying Tang; Xinmin Liu; Fengxin Zhao; Yan Peng; Xinping Gao; Lin Wang; Lijing Wang; Rui Tian; Rui Li; Hang Li (Water Research, 2026)

Auxiliary-wrapper guided and multi-criteria filter based evolutionary band selection algorithm for hyperspectral image classification - Qijun Wang; Xiaowen Sun; Rui Chen; Guangyao Yan; Aibin Yan; Ye Tian; Xingyi Zhang (Swarm and Evolutionary Computation, 2026)

Preparation of high-performance reverse osmosis membrane by “bridging” polyethylene glycol with tannic acid - Tian Wang; Rui Yu; Yanqi Gan; Zihang Zhao; Mengqi Shi; Xinxia Tian (Journal of Environmental Chemical Engineering, 2026)

Antioxidant activity and emulsifying properties of Dendrobium officinale polysaccharides with distinct structural characteristics - Cunchao Zhao; Weiqian Wang; Fanrui Li; Jun Sheng; Rui He; Lijun You; Yang Tian (Food Chemistry, 2026)

Roles of vertical light-conducting carriers applied in microalgal-bacterial biofilm for enhanced nitrogen and phosphorus removal - Yong-Sen Cao; Yong-Qi Cheng; Yi Liu; Xing-Rui Zhou; Cong-Cong Tang; Zhang-Wei He; Wen-Qiong Wang; Yu Tian; Xiaochang C. Wang (Bioresource Technology, 2026)

The potential relationships between soil microbial communities and seed germination in the floodplain wetlands - Meng-Li Wang; Rui-Si Zhao; Xiao-Kan Wang; Jia-Ying Tian; Qian-Kun Hu; Long-Yi Yuan; You-Cai Xiong; Ai-Tian Ren (Plant and Soil, 2026)

Phosphorus fertilization shapes rhizosphere beneficial microbial communities and soil–plant relations in arid cotton fields of Xinjiang, China - Bin Peng; Shuai Zhao; Cong-Rui Liu; Wen-Xuan Mai; Na Zhou; Ping Zhang; Shu-Ying Wang; Xu Liu; Bao-Zhan Wang; Chang-Yan Tian (Plant and Soil, 2026)

Diagnostic Value of Fast Stroke Imaging for Salvageable Brain Tissue and Collateral Circulation in Stroke Patients - Dongxue Wang; Shuang Liang; Zhongzhen Yue; Ye Tian; Jing Zhang; Liyu Qiao; Rui Li; Junqiang Xu; Rui Chen; Fanxiang Meng; Yichao Wang (Journal of Medical and Biological Engineering, 2026)

Fabrication of Rare Earth-Doped Fe3O4/HAP Nanoparticles with Fluorescence and their Application in Food and Beverage Testing - Yulin Wang; Rui Wu; Yankun Zhang; Guanghui Tian; Jiawei Guo; Yapeng Li (Journal of Fluorescence, 2026)

How Chlorella vulgaris remove florfenicol from wastewater—— from the aspects of kinetics, mechanism, limiting factors and long-term regulation - Lin-Lan Zhuang; Kehan Zhou; Wanqing Tian; Rui Li; Yingdong Shi; Zhongzhong Wang; Jian Zhang (Water Research, 2026)

Genome-wide identification of TGA transcription factors in wheat and the TaTGA13 negatively modulates stripe rust resistance - Jiajie Liu; Rui Li; Mingjie Xiang; Xunyin Yuan; Yifan Tian; Xuanqi Zhang; Jingyao Wang; Jianhui Wu; Qingdong Zeng; Dejun Han (Plant Science, 2026)

Iron-driven synergism among microbial functional taxa facilitates recovery from denitrification toxicity - Yongzhi Zhang; Xiaoxiao Li; Linjun Gao; Ping Ye; Rui Wang; En Zhou; Tian Sun; Miaoqing Xu; Rui Wan; Xiang Li (Journal of Environmental Management, 2026)

Efficient oxygen evolution in acidic electrolysis of water using copper loaded with iridium nanoclusters - Yanan Song; Bingxin Zhang; Tai Xiang; Huabin Wang; Yong Zhang; Xiaoning Tang; Lin Tian; Rui Xu (Journal of Environmental Sciences, 2026)

Dietary components cooperate with intestinal flora to regulate food allergy - Jiaxi Yan; Li Niu; Wei Wang; Rui Gao; Jianxiong Hao; Huan Rao; Dandan Zhao; Xueqiang Liu; Wentong Xue; Yang Tian (Food Chemistry, 2026)

Single-atom Fe engineered-PANI/AC/MXene composite flow electrode for sustainable water desalination and electroplating wastewater treatment - Rui Chen; Yuzhan Luo; Hui Wang; Youyu Tian; Zhiqun Xie; Hui Wang; Zhiwei Jiang; Anqi Wang; Kai Yan; Zongsu Wei (Chemical Engineering Journal, 2026)

N6-methyladenosine attenuates tumor-associated macrophages M2 polarization via suppressing the translation of Snail - Yifan Tian; Jianxin Peng; Jiawang Zhou; Weifeng Yang; Yanxi Peng; Jianing Li; Yalan Rui; Haisheng Zhang; Guoyou Xie; Haoran Wang; Jiamin Wang; Jiexin Li; et al. (Science China Life Sciences, 2026)

Spatiotemporal dynamics of non-photosynthetic vegetation across China and their implications for carbon fluxes along climate gradients - Chunsheng Wang; Qingjiu Tian; Wenmin Zhang; Jia Tian; Lili Chang; Rui Zhang; Qianjing Li (Science China Earth Sciences, 2026)

Warming and precipitation alter soil viral community structure and functional characteristics in dryland wheat fields on the Loess Plateau, China - Jin Kou; Feiyan Zheng; Jiaxuan Lei; Ting Wang; Heling Wang; Kai Zhang; Rui Tian; Xiaodong Lyu (Plant and Soil, 2026)

Mechanistic Integration of Beta-Alanine–Carnosine Buffering and Glutamine Metabolism in Exercise-Induced Muscle–Brain Crosstalk: Implications for Aging, Neurodegeneration, and Cognitive Decline - Rui Wang; Yan Guo; Juan Li; Tian Peng; Xinghao Wang (Molecular Neurobiology, 2026)

Echinacoside Improves Memory Function and Bone Mineral Density in the Aged SAMP8 Mouse Model - Rong Zhou; Ge Tian; Jing Yu; Rui Wang; Ning Peng; Xingzhi Guo; Rui Li (Molecular Neurobiology, 2026)

Discovery of lignans and curcuminoids as the effective inhibitors of pancreatic lipase: structure-activity relationship and inhibitory mechanism - Jie Mu; Rui-Dong Wang; Yi-Shu Zhao; Tian-Chi Lu; Si-Si Chen; Yi-Jing Wang; Hua Wei; Li-Wei Zou (Natural Product Research, 2025)

Robust building wireframe reconstruction: a hypergraph and transformer-enhanced framework for large-scale and real-world urban point clouds - Haoran Gong; Jing Liu; Rui Tong; Fuqiang Tian; Di Wang (International Journal of Remote Sensing, 2025)

Dielectric heating technology assisted for multi-objective processing of agricultural products: research progress, challenges, and future perspectives - Mengge Li; Yingqi Tian; Gaoji Yang; Liumin Fan; Longlong Jiang; Rui Li; Shaojin Wang (Critical Reviews in Food Science and Nutrition, 2025)

Performance of heavy metals in the intertidal zone surface sediments of the Yellow River Estuary under water-sediment regulation scheme - Shan Shan Liu; Jin Ming Song; Xue Gang Li; Hua Mao Yuan; Li Qin Duan; Jun Ma; Feng Min Pan; Jian Wei Xing; Chen Long Feng; De Tong Tian; Zhi Bo Wang; Rui Wang (Marine Pollution Bulletin, 2025)

New insights into sink-source dynamics of mangrove for microplastics: Quantitative evidences from field observation and resuspension simulation - Rui Li; Chao Yan; Qirui Wu; Xiangmei Cheng; Hua Wang; Zaizhi Yang; Zuobing Liang; Di Tian; Ning Yuan; Lei Hou; Lei Gao (Journal of Hazardous Materials, 2025)

Molecular sensory basis of the smoky aroma in sesame oil elucidated by combining SAFE-GC-O-MS, σ-τ plot, and computational simulations - Tian-Pei Zhao; Tong-Yu Wang; Yi Jiang; Yi-Fei Wang; Shu-Rui Zhang; Jing-Yu Chen; Yue-Hua Li; Xue-De Wang; Hua-Min Liu; Hong-Wei Liu; Ke-Qing Liu (Food Research International, 2025)

DoLPHiN: a proposed architecture and technical implementation of a database of structural and functional properties of natural polysaccharides with health benefits - Yefu Xin; Yongling Cao; Shuheng Yang; Junhao Hu; Miao Tian; Jian Dai; Jing Shi; Bingcong Yu; Nike Gu; Xiangxu Hu; Rui Zhu; Qianni Duan; et al. (Food Chemistry, 2025)

A high strength, breathable, water resistant chitosan-gelatin composite film modified by tannic acid-synergistic ZIF-8 for blueberry preservation - Huixuan Zhang; Xue Yang; Yingying Zhang; E. Zhao; Haimiao Tian; Keshan Wang; Ning Ji; Yuanyuan Liu; Rui Wang (Food Packaging and Shelf Life, 2025)

Imidacloprid induces abnormal glucose metabolism through NF-κB-mediated apoptosis of pancreatic β cells based on population exposure levels - Zhongyuan Zhang; Jiaming Fu; Yihong Di; Honghui Li; Bing Wu; Xueyan Tian; Meiyan Li; Yuqing Dai; Zhuoheng Shen; Jinhao Jia; Zeyang Bai; Limeng Xiong; et al. (Environmental Research, 2025)

Recent advances in manganese-based materials for water remediation: Multipollutant adsorption and catalytic oxidation - Hanghang Wang; Guangfei Qu; Yingying Cai; Chenyang Yin; Yaxin Tian; Rui Xu; Xinxin Liu; Minjie He; Changyi He; Jiao Wei (Environmental Research, 2025)

Superacid polymer electrolyte with end-group-protected proton sites mitigates ammonia poisoning for efficient electrochemical hydrogen separation from ammonia cracking reformate gas - Jiaqi Shuai; Hao Li; Zhengrui Xiao; Zeqi You; Yucong Liao; Rui Wang; Yafeng Li; Yuanwei Yan; Jiangping Song; Tian Tian; Lan Zhang; Siew Hwa Chan; et al. (Chemical Engineering Journal, 2025)

A pH/ROS dual-responsive hydrogel promotes diabetic wound healing by controlled release of O2 and EGCG to induce angiogenesis and immunomodulation - Yongcen Chen; Xuemin Ma; Yajuan Hu; Huiyue Wang; Peirong Zhou; Xiaoping Tian; Haofeng Wang; Yun He; Gang Tao; Rui Cai; Junliang Chen (Chemical Engineering Journal, 2025)

Corrigendum to “Porphyrinized carbon quantum dots: A novel antibacterial nanomaterial for visualized and broad-spectrum treatment of drug-resistant infected wounds” [Chem. Eng. J. Volume 522, 15 October 2025, 166981] - Mengwei Zhang; Jingjing Ye; Jingyao Zhang; Zijian Tian; Lebin Gan; Qiang Wang; Rui Li; Diya Sun; Zishuo Pei; Ming Li; Minghui Liang; Tianbing Wang (Chemical Engineering Journal, 2025)

CRP and HNF1A collaborate to regulate the progression of laryngeal cancer through the Wnt signaling pathway - Zhigang Zhao; Xiaojing Zhu; Jinyuan Xu; Penglong Song; Yanan Sun; Zhenming Yang; Li Wang; Jiarui Zhang; Rui Zhao; Xiaoxue Chen; Wenjing Li; Linli Tian; et al. (Functional & Integrative Genomics, 2025)

Unveiling Differences in Source Apportionment and Optical Properties of Wintertime Carbonaceous Aerosols in Northern and Southern Chinese Cities - Rui Li; Qiyuan Wang; Jie Tian; Yong Zhang; TingTing Wu; Lu Qi; Yang Chen; Shaofei Kong; Suixin Liu; Jin Wang; Julian Shi; Yuemei Han; et al. (Aerosol Science and Engineering, 2025)

Air layer-engineered Cf@void@SiCnf composites for enhanced electromagnetic wave absorption - Wenzhao Geng; Limeng Song; Yilin Liu; Haoyuan Lei; Peng Liang; Linan Wang; Hailong Wang; Yanqiu Zhu; Mi Tian; Rui Zhang; Zhiyu Min; Bingbing Fan (Chemical Engineering Journal, 2025)

Vertical distribution, optical properties, and source attribution of summer dust in southern Tajikistan: ground-based observations and model results - Zhongwei Huang; Qingqing Dong; Tian Zhou; Jianrong Bi; Rui Chen; Qiantao Liu; Sabur F. Abdullaev; Dilovar Nozirov; Khan Alam; Tianhe Wang; Wuren Li; Ze Li; et al. (Atmospheric Environment, 2025)

Rapid recovery of bisphenol A-inhibited anammox biofilm systems by exogenous AHLs addition - Shaopo Wang; Ruimin Tian; Yanmeng Bi; Fansheng Meng; Rui Zhang; Chenchen Wang; Dong Wang; Lingjie Liu; Xiangyu Zhang; Xinpei Guan (Journal of Water Process Engineering, 2025)

Comparative effects of improved schemes with shape adjustment and composite packaging on radio frequency heating of two-component rice - Yingqi Tian; Mengge Li; Jiahong Yuan; Dongsheng Hu; Rui Li; Hosahalli Ramaswamy; Shaojin Wang (Innovative Food Science & Emerging Technologies, 2025)

Recent research progress of methane dry reforming to syngas - Yan Wang; Rui Li; Chunyang Zeng; Wenjuan Sun; Hui Fan; Qingxiang Ma; Tian-Sheng Zhao (Fuel, 2025)

Effect of radio frequency heating on structure and physicochemical properties of protein and starch based on gelatinization degree of rice flour - Dongsheng Hu; Gaoji Yang; Yingqi Tian; Mengge Li; Liumin Fan; Rui Li; Shaojin Wang (Food Research International, 2025)

Gel-fouling on the microfiltration membrane for wastewater reclamation and its suppression by using electric fields: from the viewpoints of spatiotemporal and force analysis - Xinran Wang; Rui Wang; Xiangyu Tian; Qi Shen; Liang Feng; Dingyu Xing (Environmental Research, 2025)

Surface oxygen vacancies and their synergy effect with Pt in Pt/CoCeOx promoting H2 activation for furfural hydrogenation - Yu Fang; Rui Wang; Min Tian; Shanyu Yi; Luna Ruan; Xin Duan; Huan Zhang; Zhiqing Yang; Hengqiang Ye; Lihua Zhu (Chemical Engineering Journal, 2025)

Ultra-long and rapid operating zinc metal batteries enabled by multifunctional polarizable interface stabilizer - Song-Lin Tian; Li Lin; Si-Yu Jiang; Li-Na Song; Hai-Rui Wang; Ping Nie; Li-Min Chang; Wan-Qiang Liu (Chemical Engineering Journal, 2025)

Stabilizing zinc anode with multifunctional glycine copper additive - Lang Chen; Yue Tian; Bing-Chen Liu; Bo-Xuan Zhang; Kang-Rui Ren; Zhuo-Yun Song; Pengfei Wang; Zonglin Liu; Qianyu Zhang; Jie Shu; Ting-Feng Yi (Chemical Engineering Journal, 2025)

Porphyrinized carbon quantum dots: A novel antibacterial nanomaterial for visualized and broad-spectrum treatment of drug-resistant infected wounds - Mengwei Zhang; Jingjing Ye; Jingyao Zhang; Zijian Tian; Lebin Gan; Qiang Wang; Rui Li; Diya Sun; Zishuo Pei; Ming Li; Minghui Liang; Tianbing Wang (Chemical Engineering Journal, 2025)

Global response of soil phosphatase activity to land reclamation and vegetation restoration - Huaisong Wang; Mingming Wang; Jialing Xu; Yibo Tian; Jinyu Bai; Lei Zhang; Lianxuan Shi; Jixun Guo; Yingzhi Gao; Rui Guo; Tao Zhang (CATENA, 2025)

Differences in the home-field effects of litter decomposition modulate changes in soil microbial nutrient limitations: insights from eco-enzyme stoichiometry - Yongxia Meng; Peng Li; Lie Xiao; Jialiang Liu; Chaoya Zhang; Shutong Yang; Xiaoming Zhang; Yunqi Wang; Tian Wang; Rui Wang (CATENA, 2025)

Self-feedback cascading DNA circuit encapsulated within a gene-modified bifunctional virus-inspired nanovector for light-gated spatiotemporal biosensing in live organisms - Xiao-Xue Chen; Yong-Yao Song; Zhuo Chen; Tian-Tian Zhang; Wei-Lin Chen; Xiao-Mei Wang; Jun-Rui Hu; Cheng-Yu Li (Analytica Chimica Acta, 2025)

Acute high-altitude hypoxia induced NLRP3 inflammasome activation in pulmonary artery smooth muscle cells by BMAL1 targeting mitochondrial VDAC1-mediated MtDNA leakage - Si-Yuan He; Ying-Rui Bu; Jin Xu; Yu-Meng Wang; Tian-Xi Feng; Pei-Jie Li; Yi-Xiao Zhao; Yi-Ling Ge; Man-Jiang Xie (Apoptosis, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

B2G: A novel framework for froth velocity estimation and quantification with graph neural networks - Rui Tian; Ziqi Lv; Xiu Liu; Meijie Sun; Yanan Tu; Zhiqiang Xu; Weidong Wang (Minerals Engineering, 2025)

Mechanistic insights into electric field-driven specific ion effects on nanoplastics aggregation in heavy metal co-contaminated aquatic systems - Yan Peng; Rui Li; Ying Tang; Xinmin Liu; Yaowu Zhang; Xinping Gao; Kai Wang; Rui Tian; Hang Li (Journal of Hazardous Materials, 2025)

Cr(VI)-bioremediation mechanism of a novel strain Bacillus sp. Cr02 with simultaneous aerobic/anaerobic reduction for Cr(VI) from soil to groundwater - Liping Liu; Rui Liu; Fang Wang; Yujun Wu; Fei Ge; Jiang Tian; Feng Li; Shengguo Xue (Journal of Hazardous Materials, 2025)

Self-powered Ag2Se/SiO2/Si heterojunctions for ultrafast broadband high-sensitivity photodetection - Weipeng Shi; Rui Guo; Gailing Tian; Wenjing Zhang; Yi Chen; Wenyan Wang; Yonghua Wang; Danfeng Cui; Jinglong Wen; Dan Liu; Chenyang Xue (Chemical Engineering Journal, 2025)

A vision foundation model-based method for large-scale forest disturbance mapping using time series Sentinel-1 SAR data - Yuping Tian; Feng Zhao; Ran Meng; Rui Sun; Yuan Zhang; Yanyan Shen; Bin Wang; Jie Liu; Mingze Li (Remote Sensing of Environment, 2025)

Dietary Houttuynia cordata Thunb. extract supplementation influences on antioxidant enzymes, meat quality, and gene expressions in fresh rabbit Longissimus thoracis et lumborum meat - Xu Wang; Shuanglong Xie; Rui Chen; Jixiao Qin; Yiqing Xu; Chao Ban; Qi Lu; Xingzhou Tian (Meat Science, 2025)

Prediction and changing patterns of physicochemical properties of rice flour during radio frequency heating - Dongsheng Hu; Jiahong Yuan; Mengge Li; Yingqi Tian; Gaoji Yang; Liumin Fan; Rui Li; Shaojin Wang (Innovative Food Science & Emerging Technologies, 2025)

Failure mechanism of anchored anti-dip rock slope subjected to strong earthquakes: Insights from large-scale shaking table tests - Shanbai Wu; Liangqing Wang; Hans-Balder Havenith; Jianlin Tian; Qiong Wu; Changdong Li; Rui Ke; Chenlu Wang; Xiaochao Bi (Engineering Geology, 2025)

Females adapted better than males in Populus deltoides to simulated nitrogen deposition - Fang He; Shu-Ying Wei; Rui-Quan Wang; Jia Yao Tang; Peng Yang; Ting Wang; Jin-Liang Huang; Gang Chen; Tian-Tian Lin (Plant and Soil, 2025)

Association between serum elementomics of 48 elements and female fecundity: evidence from a nested case-control study in China - Tian Tian; Fang Liu; Li Li; Jing Wei; Kailibinuer Kayimu; Yu Fu; Huahua Jiang; Fei Kong; Rui Yang; Yuanyuan Wang; Xiaoyu Long; Jie Qiao (International Journal of Hygiene and Environmental Health, 2025)

Sensitivity analysis of system condition, sample structure, and material property to radio frequency heating characteristics of multi-component rice using computer simulation - Yingqi Tian; Mengge Li; Jinsong Zhang; Dongsheng Hu; Rui Li; Hosahalli Ramaswamy; Shaojin Wang (Innovative Food Science & Emerging Technologies, 2025)

Contrasting Effects of Warming and Nitrogen Addition on soil CO2 Emission in a Semi-Arid Grassland on the Loess Plateau of China - Mingfeng Jiang; Zhun Tian; Rui Wang; Zihan Sun; Yang Peng; Chao Fang (Water, Air, & Soil Pollution, 2025)

Functional shift in soil microbiome with decline in photosynthetic carbon input signifies rapid decrease of soil organic carbon during alpine grassland degradation - Minghua Song; Rui Pang; Yuqiang Tian; Yikang Li; Guiqiang Wang; Xingliang Xu (Biology and Fertility of Soils, 2025)

Assessing CO2 storage mechanisms in marine shallow sediments to mitigate leakage risks from sub-seabed carbon storage: a numerical simulation study - Gang Hu; Xiangyi Yi; Xuanhua Tian; Rui Wang; Pengchun Li; Linxiong Peng; Xi Liang (Frontiers in Marine Science, 2025)
The geological storage of CO 2 in offshore saline aquifers has been implemented at various sites worldwide. While subsea sediments can serve as a critical barrier against potential leakage from deep storage formations, the mechanisms and storage capacity for CO 2 trapping within these sediments remain inadequately understood. This study developed a two-dimensional conceptual model of shallow sediments based on the Enping15–1 Carbon Capture and Storage (CCS) project site in the South China Sea. Furthermore, the CO 2 -water-rock reaction and storage mechanism were simulated using CMG-GEM, and the process of CO 2 leakage into the sediments was investigated. The results indicate that CO 2 leakage into the shallow seabed sediments is primarily sequestered through dissolution in pore water, accounting for 70% of the total sequestration, while residual and mineral trapping contribute 10–20%. The dissolution of CO 2 leads to pore water acidification, which triggers the dissolution of anorthite and K-feldspar under the prevailing initial geochemical conditions. Dynamic reaction behavior is mainly observed at the leading edge of the acidified plume. However, if the leakage rate exceeds a critical threshold, the advancing acidified plume front causes partial dissolution of previously precipitated carbonate minerals. The critical leakage rate is determined to be 0.2 m³/day for single-point leakage and 0.3 m³/day for multi-point leakage. Notably, multi-point, low-velocity leakage enhances secondary storage within the sediment, thereby reducing the risk of CO 2 release into the overlying seawater.

Identification of key genes linking bisphenols exposure and breast cancer - Zhen Wang; Meng Cao; Tian Gao; Xinyue Xu; Weihua Yu; Jiangzheng Liu; Rui Liu; Xiaodi Zhang; Fei Li; Chunxu Hai (Toxicology, 2025)

The synthesis of arylmethylene bisindoles catalyzed by nickel perchlorate as potential antifungal agent against Clarireedia homoeocarpa - Ye Zhou; Ruyuan Wang; Rui Feng; Bi Wang; Shu Xu; Mei Tian; Wenhao Liang; Jin Chen; Yu Chen; Xu Feng; Li Lin; Jinyue Luo; et al. (Phytochemistry Letters, 2025)

Cement-mortar lining failure and metal release caused by electrochemical corrosion of ductile iron pipes in drinking water distribution systems - Hao Guo; Rui Wang; Menghan Jiang; Yimei Tian; Yapeng Jin; Weigao Zhao; Chenwan Wang; Jianhua Yin (Journal of Environmental Sciences, 2025)

Enhanced gut damage and microbial imbalance in bullfrog tadpoles (Lithobates catesbeiana) exposed to polystyrene microplastics under high-temperature conditions - Zhilong Wang; Jun Xie; Guangjun Wang; Huirong Yang; Zhifei Li; Kai Zhang; Rui Shu; Wenping Xie; Jingjing Tian; Hongyan Li; Wangbao Gong; Yun Xia (Environmental Pollution, 2025)

Field and numerical investigations on linkage failure of the main roof and pumpable supports in the pre-excavation recovery room - Dong Zhang; Jianbiao Bai; Yonghong Guo; Zizheng Zhang; Rui Wang; Zhijun Tian; Shuai Yan; Qiancheng Zhu; Min Deng; Hao Fu; Shuaigang Liu (Engineering Geology, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

High Yield of Prodigiosin by Serratia marcescens Ka3 Using Additive Huangshui, a Byproduct of Chinese Liquor (Baijiu) - Chuan Wang; Zhongxing Gao; Rui Han; Yaomei Tian; Hongjun Fan; Yuliang Zhang (Current Microbiology, 2025)

Cascading environmental, phenological, and physiological influences on spatial variability of annual gross primary productivity in the Northern Hemisphere - Lang Han; Gui-Rui Yu; Zhi Chen; Qiu-Feng Wang; Xian-Jin Zhu; Wei-Kang Zhang; Tie-Jun Wang; Zhi-Feng Yan; Tian-You Zhang; Shi-Ping Chen; Hui-Min Wang; Jun-Hua Yan; et al. (Science of The Total Environment, 2025)

Computer simulation analysis to improve radio frequency heating uniformity of multi-component rice samples by screening of sample structure - Yingqi Tian; Mengge Li; Longlong Jiang; Rui Li; Hosahalli Ramaswamy; Shaojin Wang (Innovative Food Science & Emerging Technologies, 2025)

Low perception of climate change by farmers and herders on Tibetan Plateau - Jiawei Yi; Yuan Tian; Nicholas P. Simpson; Yunyan Du; Ting Ma; Chengqun Yu; Talbot M. Andrews; Tao Pei; Xinjie Zha; Chenghu Zhou; Wei Sun; Shaowei Li; et al. (Global Environmental Change, 2025)

Combining the bridging effect of tannic acid and solution activation for improving the lithium/magnesium separation performance of nanofiltration membrane - Tian Wang; Yajiao Long; Rui Yu; Yanqi Gan; Haonan Zhang; Jiahe Li; Mengqi Shi (Desalination, 2025)

The application of marine bioactive composite materials in environmental remediation - Yanan Huang; Hao Li; Ronglian Xing; Xiaorui Chen; Yuxin Sun; Meichen Tian; Ran Zhang; Xin Wang; Xinxin Wang; Rui Li; Lihong Chen; Hongxia Zhang; et al. (Desalination, 2025)

Physical-washable Revivable biomass membrane with high separation Rates against harsh conditions for sustainable treatment of wastewater containing emulsified oil - Yunhao Pan; Tiancheng Zha; Yanan Zhu; Yibo Zhang; Xunming Tian; Aiwen Wang; Rui Wang; Dongmei Liu; Wei Wang; Shouzhu Li (Chemical Engineering Journal, 2025)

The tumor suppressor SALL2 opposes chemotherapeutic resistance in breast cancer - Qiji Li; Chenxin Li; Yuhao Zhang; Zihan Zheng; Yun Wang; Yingqian Yang; Qingqing Zhu; Rui Wang; Wanhui Xu; Chengming Zhu; Qin Tian; Meng Wang; et al. (Molecular and Cellular Biochemistry, 2025)

CORBES: Radiation belt survey with international small satellite constellation - Ji Wu; Li Deng; Jaan Praks; Marius Anger; Philipp Oleynik; Wojciech Hajdas; Jin-Dong Wang; Shen-Yi Zhang; Bin Zhou; Li Zeng; Jinbin Cao; David Fischer; et al. (Advances in Space Research, 2025)

Evaluating the Centre‐Periphery Hypothesis Through Genomic Phylogeographical Comparisons of Two Sister Species of Liquidambar in East Asia's Tertiary Relict Forests - Tian‐Rui Wang; Wu‐Qin Xu; Hans‐Peter Comes; Xin‐Yi Zhang; Jun Chen; Yin‐Gang Li; Ying‐Xiong Qiu (Journal of Biogeography, 2025)
Aim Understanding the spatial distribution of genetic variation within species is a central tenet in evolutionary biology and conservation biology. This study explores how historical demographic processes and/or environmental factors interact to affect contemporary genetic variation and adaptive potential, with a specific focus on testing the ‘centre‐periphery’ hypothesis (CPH). Location Subtropical China. Taxon Liquidambar. Methods We combined comparative phylogeography, landscape genomics and niche modelling to investigate the interplay between demographic history and past/current environmental factors in shaping genetic variation in Liquidambar formosana and L. acalycina , a sister pair of East Asia's Tertiary relict forests. Results In both species, core populations occupied highly suitable habitats at highest densities. Consistent with the CPH, population genetic diversity decreased, and differentiation increased, from centre to margin in L. acalycina , but not in L. formosana , likely reflecting different demographic histories and different relative contributions of geography, past (LGM) and current climates to their present‐day genetic variation. In addition, L. formosana showed higher adaptive potential to future climate change than L. acalycina . Main Conclusions This study demonstrates that differences in contemporary genetic variation and adaptability among closely related species can be explained by contrasting demographic responses to multiple geographic/climatic factors. In turn, it should also expand our understanding of the CPH, while informing future conservation efforts for these two study species.

TadpoleTraits : A Global Database on Morphological Traits of Tadpoles of Anura - Yanfang Song; Rui Tian; Yongle Wang; Pingfan Wei; Tao Zhang; Shuaiwei Luo; Zhiyong Yuan; Weiwei Zhou (Global Ecology and Biogeography, 2025)
Motivation Functional diversity is an important dimension of biodiversity. In animals, most species have complex life cycles, such that the same species can display great differences in traits and ecological roles across different life history stages. Consequently, the patterns and driving factors of functional diversity can vary considerably among the different life stages. However, research on stages other than adults is rare, with data scarcity being a potential reason. The order Anura of Amphibia is a highly diverse group of terrestrial vertebrates, comprising more than 7800 species. Anurans have complex life cycles, and our knowledge about functional traits of the larval stage is extremely limited. To fill this gap, we collected morphological traits of tadpoles globally and compiled a database covering 1993 species to facilitate future studies. This database can help us gain a more comprehensive understanding of anuran biodiversity. Additionally, it offers a valuable tool for testing ecological and evolutionary hypotheses related to complex life cycles in animals. Main Types of Variables Contained Twenty‐three traits collected from literature and 11 traits obtained by image measuring. Spatial Location and Grain Global. Major Taxa and Level of Measurement Anura, species. Software Format xlsx.

Predictive maintenance for offshore wind farms with incomplete and biased prognostic information - Rui He; Zhigang Tian; Yifei Wang; Yinuo Chen; Ming J. Zuo (Ocean Engineering, 2025)

A novel tannic acid/iron/hydrophilic polymer nanofiltration membrane for small organic pollutant/salt separation - Yajiao Long; Yanqi Gan; Xiong Yao; Tian Wang; Haonan Zhang; Rui Yu; Jiahe Li; Mengqi Shi (Journal of Environmental Chemical Engineering, 2025)

New insight into the role of bisphenol A on the anammox system: Oxidative stress and quorum sensing mechanisms - Yu Tian; Lingjie Liu; Chunsheng Qiu; Dong Wang; Rui Zhang; Yanmeng Bi; Shaopo Wang; Bo Zhang (Journal of Environmental Chemical Engineering, 2025)

Grazing and Enclosure Alter the Vertical Distribution of Bacterial Communities in Different Microhabitats of Wetlands Along the Xilin River - Xiaoai Cao; Yating Tian; Huamin Liu; Hongbo Yu; Feng Niu; Rui Zhang; Zhichao Xu; Yi Zhuo; Lu Wen; Dongwei Liu; Lixin Wang (Wetlands, 2025)

Comparative chloroplast genome analysis of the medicinal species in Rubus: Insights into genomic characterization and phylogenetic relationships - Jiayu Jiang; Rui Tian; Ruolan Wang; Shuang Wang; Dequan Zhang (Plant Systematics and Evolution, 2025)

Specific cation effects on soil water infiltration and soil aggregate stability–Comparison study on variably and permanently charged soils - Shishu Yang; Rui Tian; Haiyang Wang; Yekun Zhang; Hang Li (Soil and Tillage Research, 2025)

Gelation melioration of clam Meretrix meretrix surimi based on the interactions with different plant/animal proteins - Lin-Da Zhang; Yue Liu; Ying-Rui Wang; Tian-Qi Zhou; Jia-Cheng Liu; Jia-Nan Yan; Bin Lai; Ce Wang; Hai-Tao Wu (Food Chemistry, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Effect of torrefaction pretreatment on catalytic pyrolysis of bagasse: A study on torrefaction method and atmosphere - Rui Liao; Xiaojie Tian; Liangliang Fan; Hui Li; Yuan Zeng; Linyao Ke; Qiuhao Wu; Roger Ruan; Yuhuan Liu; Yunpu Wang (Chemical Engineering Journal, 2025)

Recyclable thermally conductive nanocomposites based on interpenetrating network of boron nitride nanosheets and nanoribbons - Caiyue Huang; Xiaohua Jia; Rui Tian; Zhaofeng Wang; Haojie Song (Chemical Engineering Journal, 2025)

Experiment and Peridynamics Simulation on Failure Mechanical Behavior of Cylindrical Sandstone Containing Two Persisting Fissures Under Conventional Triaxial Compression - Sheng-Qi Yang; Heng Li; Shi-Gui Du; Rui Yong; Su-Sheng Wang; Wen-Ling Tian; Yun-Jin Hu; Yong Niu (Rock Mechanics and Rock Engineering, 2025)

Taloring sawdust derived hydrochar via red mud for cadmium removal: Electron transfer insight and recyclability assessment - Ting Cui; Dingxiang Chen; Ran Duan; Fan Yang; Danting Li; Lin Tian; Yong Zhang; Huabin Wang; Rui Xu (Chemosphere, 2025)

Chicken adipose tissue is differentially involved in primary and secondary regional immune response to NDV through miR-20a-5p-NR4A3 pathway - Yi Jiang; Rui Zhang; Xinxin Xu; Xiangnan Wang; Yufei Tian; Wei Zhang; Xiaoli Ma; Chaolai Man (Veterinary Immunology and Immunopathology, 2025)

Parametric investigation of suction actuators on the tunnel wall for alleviating pressure interactions in high-speed maglev train/tunnel system - Zheng-Wei Chen; Zhan-Hao Guo; Yi-Qing Ni; Zi-Jian Guo; Tian-Tian Wang; En-Ze Rui; Guang-Zhi Zeng (Tunnelling and Underground Space Technology, 2025)

Development and characterization of a γ-PGA/PVA/SDBS cross-linked network foam for dust suppression in tunneling construction - Xinjiao Tian; Yixiang Huang; Qiang Zhang; Hongxiang Wang; Jinqian Zeng; Chaoqun Yuan; Jiefeng Pan; Rui Wang; Zhenming Li (Journal of Environmental Chemical Engineering, 2025)

Gelation improvement of low-salt Chinese shrimp (Fenneropenaeus chinensis) surimi gel by L-arginine - Yue Liu; Lin-Da Zhang; Ying-Rui Wang; Tian-Qi Zhou; Yu-Qiao Wang; Jia-Nan Yan; Bin Lai; Ce Wang; Hai-Tao Wu (Food Chemistry, 2025)

Radio frequency inactivation of Bacillus cereus and natural microbiota in brown rice: Evaluation of inactivation kinetics and germination capacity - Gaoji Yang; Dingting Zhou; Juanjuan Xu; Yingqi Tian; Rui Li; Shaojin Wang (Food Control, 2025)

Deciphering the mineral code of urinary stones: A first look at zinc isotopes - Ziyang Ding; Guilin Han; Yu Tian; Rui Qu; Jinke Liu; Di Wang; Ye Zhao (Environmental Pollution, 2025)

Two-stage continuous cultivation of microalgae overexpressing cytochrome P450 improves nitrogen and antibiotics removal from livestock and poultry wastewater - Rui Xiao; Chang Tian; Haijun Wang; Hui Zhang; Huan Chen; Howard H. Chou (Bioresource Technology, 2025)

The Effect of Disc Degeneration on the Biomechanical Response of the Lumbar Spine under Vibration Loading Condition - Bin Zhang; Tian-Cheng Li; Xin Wang; Rui Zhu; Cheng-Fei Du; Yuan Xie (Journal of Medical and Biological Engineering, 2025)

Sleep deprivation stimulates adaptive thermogenesis by activating AMPK pathway in mice - Tian-Shu Zheng; Xin-Ran Gao; Rui-Ping Xu; Yi-Fei Zhao; Zhi-Teng Yang; De-Hua Wang (Journal of Comparative Physiology B, 2025)

Molecular mechanisms behind the inhibitory effects of ginsenoside Rg3 on hepatic fibrosis: a review - Zhao-feng Tian; Rui-yi Hu; Zi Wang; Ya-jun Wang; Wei Li (Archives of Toxicology, 2025)

An effective strategy for high-value utilization of chromite ore processing residue (COPR) through reductive alkali roasting and physical separation - Cheng Tian; Cunfang Lu; Jun Yang; Rui Xu; Min Zhang; Juan Wen; Yelei Wang; Shuo Zhang; Yuanyuan He; Dan Luo; Huazheng Luo; Xingran Zhang (Process Safety and Environmental Protection, 2025)

Numerical investigation on the suction caisson response considering seabed trenches and cyclic loading - Le Wang; Tingran Zhang; Xinglei Cheng; Wanhai Xu; Zhichao Shen; Shengjie Rui; Yinghui Tian (Ocean Engineering, 2025)

Organic matter accumulation driven by land-sea interactions during the Late Cretaceous: A geochemical study of the Nenjiang Formation, Songliao Basin - Congsheng Bian; Shiju Liu; Wei Liu; Xiong Cheng; Xin Liu; Jin Dong; Rui Wang; Yongxin Li; Ming Guan; Qianhui Tian; Wenzhi Zhao (Organic Geochemistry, 2025)

Energy-saving extractive distillation processes design and optimization for the separation of ethyl acetate and n-heptane azeotrope - Xin Tian; Rui Wang; Honghai Wang; Chunli Li; Jiapeng Liu (Fuel, 2025)

A multirisk-rescued biomimetic nanozyme against periodontitis via inflammation targeting and microenvironment reprogramming - Lin Li; Rui-Xin Wu; Jia Wang; Rui Jin; Xin-Yu Zhang; Mei Xu; Si-Yao Li; Rui Gao; Bei-Min Tian; Xiao-Tao He; Fa-Ming Chen; Yuan Yin (Chemical Engineering Journal, 2025)

Readily recyclable, degradable, stretchable, highly conductive, anti-freezing and anti-drying glycerohydrogel for triboelectric nanogenerator - Sihan Jiang; Yang Wang; Meiqin Tian; Haiyang Zhang; Rui Wang; Haokun Yan; Hao Tan; Rasoul Esmaeely Neisiany; Wei Sun; Zhengwei You (Chemical Engineering Journal, 2025)

A combined strategy of brain neuroprotection and endogenous neuroregeneration for enhanced intracerebral hemorrhage treatment via an injectable biomimetic hydrogel with efficient ROS scavenging and therapeutics delivery - Jiake Xu; Luyao Wan; Xueqi Wang; Yang Wei; Yinhai He; Shenglan You; Rui Zhong; Chengwei Wang; Hao Li; Chao You; Meng Tian (Chemical Engineering Journal, 2025)

Therapeutic Potential of Mesenchymal Stem Cell-Derived Exosomes in Spinal Cord Injury - Jing An; Bo Chen; Rui Zhang; Ding Tian; Kuohao Shi; Lingling Zhang; Gaorong Zhang; Jingchao Wang; Hao Yang (Molecular Neurobiology, 2025)

Insight into the effect of humic acids on transport of Cd2+ in biochar-amended saturated porous media - Tian Zhao; Yongyang Liu; Rui Liu; Fang Wang (Journal of Soils and Sediments, 2025)

SOTHE: SOlar-terrestrial habitability explorer - Jiajia Liu; Bingkun Yu; Fuchuan Pang; Siteng Fan; Lixiang Gu; Lingping He; Yajuan Lei; Bo Li; Rui Li; Yiren Li; Dongdong Liu; Kai Liu; et al. (Advances in Space Research, 2025)

Associations between volatile organic compounds exposure and multiple oxidative damage biomarkers: Method development, human exposure, and application for e-waste pollution prediction - Jia-Rong Wang; Hong-Xuan Kuang; Ye Liu; Xin-Yi Li; Tian-Hong Chen; Xiao-Hui Zhu; Rui-Fang Fan; Ming-Deng Xiang; Yun-Jiang Yu (Science of The Total Environment, 2024)

Contractor-oriented optimization for wind farm maintenance decision-making considering partial monitoring information and degraded working efficiency - Yifei Wang; Rui He; Zhigang Tian; Yinuo Chen (Ocean Engineering, 2024)

The role of probiotics in the treatment of non-alcoholic fatty liver disease (NAFLD): New insights based on meta-analysis and subgroup analysis - Rui Xiao; Yang Cao; Linlin Wang; Peijun Tian; Qixiao Zhai; Jianxin Zhao; Gang Wang; Yu Zhu (Food Bioscience, 2024)

Corrigendum to “A critical review on graphene oxide membrane for industrial wastewater treatment” [Environ. Res. 223 (2023) 115409] - Ye-Chen An; Xiao-Xu Gao; Wen-Li Jiang; Jing-Long Han; Yuan Ye; Tian-Ming Chen; Rui-Yun Ren; Jia-Hui Zhang; Bin Liang; Zhi-Ling Li; Ai-Jie Wang; Nan-Qi Ren (Environmental Research, 2024)

Development of self-centering and energy-dissipating dual-stage reinforced concrete rocking column-base system - Genqi Xiao; Haishen Wang; Peng Pan; Hengyi Pan; Rui He; Guyu Tian (Engineering Structures, 2024)

Microalgae biofilm barrier to assist the simultaneous nitrogen and phosphorus removal in anammox: Molecular mechanism on sludge granulation and microbial metabolism - Xue Chen; Rui Hu; Mengting Xia; Shiliang Heng; Jiandong Wang; Zhaobin Liu; Jiahua Tian; Xueqin Lu; Guangyin Zhen (Chemical Engineering Journal, 2024)

Microwave pyrolysis of Choerospondias axillaris seeds with their derived biochar for comprehensive utilization of the biomass - Ruolan Zhou; Xiaojie Tian; Xiaofei Wang; Yuan Zeng; Linyao Ke; Qiuhao Wu; Rui Liao; Roger Ruan; Liangliang Fan; Yunpu Wang (Chemical Engineering Journal, 2024)

EGR1 transcriptionally regulates SVEP1 to promote proliferation and migration in human coronary artery smooth muscle cells - Qiang Tian; Jia-He Chen; Yi Ding; Xin-Yu Wang; Jia-Yun Qiu; Qian Cao; Li-Li Zhuang; Rui Jin; Guo-Ping Zhou (Molecular Biology Reports, 2024)

Study of the effect of keap1 on oxidative stress in human umbilical cord mesenchymal stem cells - Hongrong Deng; Yunxia Chen; Huiwen Liu; Li Wang; Hao Xu; Bin Tan; Qin Yi; Rui Wang; Bolin He; Jie Tian; Jing Zhu (Molecular Biology Reports, 2024)
Background HucMSCs had shown promising efficacy in treating childhood diseases, but oxidative stress induced by the poor microenvironment at the site of damage resulted in low cell survival after transplantation, thus preventing the cells from maximizing therapeutic efficacy. Therefore, this study aimed to investigate the role and mechanism of keap1 in oxidative stress injury of human umbilical cord mesenchymal stem cells (hucMSCs), and to provide theoretical support for improving the efficacy of stem cell therapy. Methods The hucMSCs were treated with hypoxic low-sugar-free serum (GSDH) to mimic the damaged site microenvironment after implantation. Adenoviral overexpression of keap1 gene of hucMSCs was performed in vitro, and cell proliferation ability was detected by CCK8 assay, crystal violet staining assay, and cell cycle assay. Cellular redox level was assessed by Amplex Red, MDA, and GSH/GSSG kit. Mitochondrial morphology was evaluated by mitotracker Red staining. ATP production was estimated by ATP detection kit. The mRNA and protein expression levels were tested by western blotting and RT-qPCR. Results GSDH treatment substantially upregulated keap1 expression. Subsequently, we found that overexpression of keap1 notably inhibited cell proliferation and caused cells to stagnate in G1 phase. At the same time, overexpression of keap1 induced the production of large amounts of H 2 O 2 and the accumulation of MDA, but suppressed the GSH/GSSG ratio and the expression of antioxidant proteins NQO1 and SOD1, which caused oxidative stress damage. Overexpression of keap1 induced cells to produce a large number of dysfunctional mitochondria resulting in reduced ATP production. Moreover, Overexpression of keap1 significantly decreased the IKKβ protein level, while upregulating IkB mRNA levels and downregulating P50 mRNA levels. Conclusions Overexpression of keap1 may induce oxidative stress injury in hucMSCs by down-regulating IKKβ expression and inhibiting NF-κB pathway activation. This implies the importance of keap1 in hucMSCs and it may be a potential gene for genetic modification of hucMSCs.

On the Nearshore Significant Wave Height Inversion from Video Images Based on Deep Learning - Chao Xu; Rui Li; Wei Hu; Peng Ren; Yanchen Song; Haoqiang Tian; Zhiyong Wang; Weizhen Xu; Yuning Liu (Journal of Marine Science and Engineering, 2024)
Accurate observation of nearshore waves is crucial for coastal safety. In this study, the feasibility of extracting wave information from wave video images captured by shore-based cameras using deep learning methods was explored, focusing on inverting nearshore significant wave height (SWH) from instantaneous wave video images. The accuracy of deep learning models in classifying wind wave and swell wave images was investigated, providing reliable classification results for SWH inversion research. A classification network named ResNet-SW for wave types with improved ResNet was proposed. On this basis, the impact of instantaneous wave images, meteorological factors, and oceanographic factors on SWH inversion was evaluated, and an inversion network named Inversion-Net for SWH that integrates multiple factors was proposed. The inversion performance was significantly enhanced by the specialized models for wind wave and swell. Additionally, the inversion accuracy and stability were further enhanced by improving the loss function of Inversion-Net. Ultimately, time series inversion results were synthesized from the outputs of multiple models; the final inversion results yielded a mean absolute error of 0.04 m and a mean absolute percentage error of 8.52%. Despite certain limitations, this method can still serve as a useful alternative for wave observation.

Myosuppressin signaling deficiency affects ovarian development via repression of 20-hydroxyecdysone biosynthesis in Grapholita molesta - Jie Cheng; Jing-Kai Liu; Tian-Li Wang; Wei Wei; Hui-Ming Xiang; Xian-Wei Li; Rui-Yan Ma; Zhi-Guo Zhao (Pesticide Biochemistry and Physiology, 2024)

Paleontologic, paleogeographic, and sedimentologic controls on the spatial-temporal distribution of Permian sponge reefs in South China - Xuesong Tian; Kun Liang; Olev Vinn; Dishu Chen; Feng Zhang; Rui Cao; Yue Wang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Cost-efficient breakthrough: Fabricating multifunctional woven hydrogels from water-soluble polyvinyl alcohol yarn - Chenxing Xiang; Yuanhao Tian; Huiming Ning; Ning Hu; Lidan Zhang; Feng Liu; Rui Zou; Shu Wang; Jie Wen; Leilei Li (Chemical Engineering Journal, 2024)

Rational design of chromium-doped NiFe phosphide/phosphate heterostructures for inhibiting chloride ion adsorption and achieving alkaline seawater splitting at industrial-level current density - Fanjia Sun; Yanhui Wang; Xueqing Tian; Rui Zhu; Ziliang Zhuang; Youbin Zheng; Jianbing Zang; Liang Dong (Chemical Engineering Journal, 2024)

Hybrid packed bed bioreactor using combined biodegradation and ozonation to enhance nitrogen and micropollutants removal from landfill leachate - Xuetong Yang; Ze Liu; Changtao Chen; Tao Zhang; Qintong Wang; Rui Zhang; Feng Duan; Xiang Tian; Mingshui Yao; Kristof Demeestere; Stijn W.H. Van Hulle (Bioresource Technology, 2024)

Yr29 combined with QYr.nwafu-4BL.3 confers durable resistance to stripe rust in wheat cultivar Jing 411 - Mingjie Xiang; Bo Tian; Jianghao Cao; Shengjie Liu; Caie Zhou; Xiaoting Wang; Yibo Zhang; Jiale Li; Xunying Yuan; Jufen Wan; Rui Yu; Weijun Zheng; et al. (Theoretical and Applied Genetics, 2024)

Weights embedding Informer prediction algorithm-based fault diagnosis framework for nuclear power plant - Tan Canyi; Zheng Wei; Wang Bo; Tan Sichao; Liang Biao; Li Jiangkuan; Han Rui; Ke Zhiwu; Tian Ruifeng (Annals of Nuclear Energy, 2024)

Flow Field Analysis and Development of a Prediction Model Based on Deep Learning - Yingjie Yu; Xiufeng Zhang; Lucai Wang; Rui Tian; Xiaobin Qian; Dongdong Guo; Yanwei Liu (Journal of Marine Science and Engineering, 2024)
The velocity of ocean currents significantly affects the trajectory prediction of ocean drifters and the safe navigation of intelligent vessels. Currently, most ocean current predictions focus on time-based forecasts at specific fixed points. In this study, deep learning based on the flow field prediction model (CNNs–MHA–BiLSTMs) is proposed, which predicts the changes in ocean currents by learning from historical flow fields. Unlike conventional models that focus on single-point current velocity data, the CNNs–MHA–BiLSTMs model focuses on the ocean surface current information within a specific area. The CNNs–MHA–BiLSTMs model integrates multiple convolutional neural networks (CNNs) in parallel, multi-head attention (MHA), and bidirectional long short-term memory networks (BiLSTMs). The model demonstrated exceptional modelling capabilities in handling spatiotemporal features. The proposed model was validated by comparing its predictions with those predicted by the MIKE21 flow model of the ocean area within proximity to Dalian Port (which used a commercial numerical model), as well as those predicted by other deep learning algorithms. The results showed that the model offers significant advantages and efficiency in simulating and predicting ocean surface currents. Moreover, the accuracy of regional flow field prediction improved with an increase in the number of sampling points used for training. The proposed CNNs–MHA–BiLSTMs model can provide theoretical support for maritime search and rescue, the control or path planning of Unmanned Surface Vehicles (USVs), as well as protecting offshore structures in the future.

RAD-seq data for Engelhardia roxburghiana provide insights into the palaeogeography of Hainan Island and its relationship to mainland China since the late Eocene - Pei-Han Huang; Tian-Rui Wang; Min Li; Zi-Jia Lu; Ren-Ping Su; Ou-Yan Fang; Lang Li; Shi-Shun Zhou; Yun-Hong Tan; Hong-Hu Meng; Yi-Gang Song; Jie Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Thermo-economic analysis and multi-objective optimization of cryogenic CO2 capture systems based on liquefied natural gas cold energy utilization - Gequn Shu; Borui Liu; Hua Tian; Ligeng Li; Rui Sun; Xuan Wang (Journal of Environmental Chemical Engineering, 2024)

CO2 retention in high-pressure/high-temperature reservoirs of the Yinggehai Basin, northwestern South China Sea - Jinyan Lin; Rui Liu; Niklas Heinemann; Johannes M. Miocic; Jinqiang Tian; Zengyu Chen; Lin Hu; Yazhen Zhang; Julien Amalberti; Lichao Wang (International Journal of Greenhouse Gas Control, 2024)

Developing a radio frequency-hot air spouting treatment for efficient dehydration of carrot cubes: Evaluation of the heating and moisture distribution uniformity - Junjie Zheng; Xin Ye; Longlong Jiang; Xiaojiang Wang; Mengge Li; Yingqi Tian; Rui Li; Shaojin Wang (Innovative Food Science & Emerging Technologies, 2024)

Polydopamine-assisted minute fabrication of vertically aligned ZIF-L membranes for CO2/N2 separations - Keming Zhang; Sihui Li; Xiaohe Tian; Rui Zhang; Xiaoting Feng; Qingnan Wang; Yanting Tang; Chenlu Liu; Hongxia Gao; Shaofei Wang (Chemical Engineering Journal, 2024)

Evolutionary dynamics of cooperation coupled with ecological feedback compensation - Zi-Xuan Guo; Tian-Jiao Feng; Yi Tao; Rui-Wu Wang; Xiu-Deng Zheng (BioSystems, 2024)

A Cysteinyl-tRNA Synthetase Mutation Causes Novel Autosomal-Dominant Inheritance of a Parkinsonism/Spinocerebellar-Ataxia Complex - Han-Kui Liu; Hong-Lin Hao; Hui You; Feng Feng; Xiu-Hong Qi; Xiao-Yan Huang; Bo Hou; Chang-Geng Tian; Han Wang; Huan-Ming Yang; Jian Wang; Rui Wu; et al. (Neuroscience Bulletin, 2024)
This study aimed to identify possible pathogenic genes in a 90-member family with a rare combination of multiple neurodegenerative disease phenotypes, which has not been depicted by the known neurodegenerative disease. We performed physical and neurological examinations with International Rating Scales to assess signs of ataxia, Parkinsonism, and cognitive function, as well as brain magnetic resonance imaging scans with seven sequences. We searched for co-segregations of abnormal repeat-expansion loci, pathogenic variants in known spinocerebellar ataxia-related genes, and novel rare mutations via whole-genome sequencing and linkage analysis. A rare co-segregating missense mutation in the CARS gene was validated by Sanger sequencing and the aminoacylation activity of mutant CARS was measured by spectrophotometric assay. This pedigree presented novel late-onset core characteristics including cerebellar ataxia, Parkinsonism, and pyramidal signs in all nine affected members. Brain magnetic resonance imaging showed cerebellar/pons atrophy, pontine-midline linear hyperintensity, decreased rCBF in the bilateral basal ganglia and cerebellar dentate nucleus, and hypo-intensities of the cerebellar dentate nuclei, basal ganglia, mesencephalic red nuclei, and substantia nigra, all of which suggested neurodegeneration. Whole-genome sequencing identified a novel pathogenic heterozygous mutation (E795V) in the CARS gene, meanwhile, exhibited none of the known repeat-expansions or point mutations in pathogenic genes. Remarkably, this CARS mutation causes a 20% decrease in aminoacylation activity to charge tRNA Cys with L-cysteine in protein synthesis compared with that of the wild type. All family members carrying a heterozygous mutation CARS (E795V) had the same clinical manifestations and neuropathological changes of Parkinsonism and spinocerebellar-ataxia. These findings identify novel pathogenesis of Parkinsonism-spinocerebellar ataxia and provide insights into its genetic architecture.

Effects of Different Concentrations of Weak Acid Fracturing Fluid on the Microstructure of Coal - Gan Rui; Zuo Shaojie; Si Junting; Liu Chengwei; Tian Feng; Jiang Zhizhong; Wang Changwei; Peng Shouqing; Xu Zhiyuan (Natural Resources Research, 2024)

Soil urease functional stability to Hg pollution: An ecotoxicological perspective - Hui Huang; Haixia Tian; Yan Li; Ziquan Wang; Tiantian Yang; Rui Qian; Mallavarapu Megharaj; Wenxiang He (Ecotoxicology, 2024)

Rare oxoisoaporphine alkaloids from Menispermum dauricum with potential anti-inflammatory activity - Rui Guo; Cun-Lin Wang; Xiao-Juan Cao; Xiao-Juan Yao; Xin Qiao; Ya-Tian Meng; Tong Zhang; Qiong Zhang (Phytochemistry, 2024)

A novel method of fuel consumption prediction for wing-diesel hybrid ships based on high-dimensional feature selection and improved blending ensemble learning method - Tian Lan; Lianzhong Huang; Ranqi Ma; Zhang Ruan; Shan Ma; Zhongwei Li; Haoyang Zhao; Cong Wang; Rui Zhang; Kai Wang (Ocean Engineering, 2024)

Construction of an S-scheme electron transfer channel in Cu0/CuFe2O4 magnetic plate column reactor for the LEV degradation: New strategy of visible Photo-Fenton system application - Rui Wang; Aiwen Wang; Yunhao Pan; Jiaxin Ni; Yingjie Deng; Zhe Tao; Xiongying Liang; Jingrui Tang; Xunming Tian; Tiancheng Zha; Dongmei Liu; Jun Ma (Journal of Hazardous Materials, 2024)

A fully degradable flexible membrane via green synthesis for highly effective separation of oil-water emulsions - Yunhao Pan; Tiancheng Zha; Xunming Tian; Liuqian An; Aiwen Wang; Rui Wang; Yibo Zhang; Jinxin Yao; Dongmei Liu; Shouzhu Li; Wei Wang (Chemical Engineering Journal, 2024)

Outdoor tubular photobioreactor microalgae-microorganisms biofilm treatment of municipal wastewater: Enhanced heterotrophic assimilation and synergistic aerobic denitrogenation - Pan Li; Yajun Luo; Jiansong Tian; Yiwei Cheng; Shiji Wang; Xin An; Jingxian Zheng; Heng Yan; Hongtao Duan; Jin Zhang; Zhicheng Pan; Yangwu Chen; et al. (Bioresource Technology, 2024)

Shoot and Root Traits are Associated with Varying Soil Phosphorus Supply in Chinese Cabbage - Hou Sai-sai; Pu Zi-tian; Zhang Rui-fang; Zhang Chi; Wang Hong; Wang Xin-xin; Zhao Jian-jun (Journal of Soil Science and Plant Nutrition, 2024)

PET microplastics influenced microbial community and heavy metal speciation in heavy-metal contaminated soils - Yajuan Tang; Yi Xing; Xin Wang; Haobo Ya; Tian Zhang; Mingjie Lv; Jianchao Wang; Han Zhang; Wei Dai; Duo Zhang; Rui Zheng; Bo Jiang (Applied Soil Ecology, 2024)

MARCH1 and MARCH2 inhibit pseudorabies virus replication by trapping the viral cell-to-cell fusion complex in trans-Golgi network - Rui Huang; Cui-Hong Rao; Yuan-Zhe Bai; Changqing Yu; Meng Chen; Jin-Mei Peng; Shi-Jia Xu; Yue Sun; Meng Fandan; Chuang Lyu; Mirwaise Khan; Tong-Qing An; et al. (Veterinary Microbiology, 2024)

Developing a spouted bed for combined radio frequency-hot air treatments to improve the heating uniformity in high-moisture carrot cubes - Junjie Zheng; Longlong Jiang; Xin Ye; Xiaojiang Wang; Yingqi Tian; Mengge Li; Rui Li; Shaojin Wang (Journal of Food Engineering, 2024)

Effect of BaTiO3 as a filling material with adjustable dielectric properties on improving the radio frequency heating uniformity in red jujubes - Longlong Jiang; Junjie Zheng; Mengge Li; Yingqi Tian; Xiaojiang Wang; Rui Li; Shaojin Wang (Journal of Food Engineering, 2024)

Developing effective radio frequency drying processes for tiger nuts: Dynamic analysis of moisture state, dielectric properties and quality - Mengge Li; Yingqi Tian; Longlong Jiang; Juanjuan Xu; Rui Li; Shaojin Wang (Journal of Food Engineering, 2024)

Extended applications of the small-scale radio frequency system for improving the heating performance of multi-component rice - Yingqi Tian; Haibo Yu; Mengge Li; Longlong Jiang; Rui Li; Hosahalli Ramaswamy; Shaojin Wang (Innovative Food Science & Emerging Technologies, 2024)

Slide-controlling modes and classification system of the mélange high slopes: insight into a disaster-causing mechanism of the Jinsha River mélange belt in the eastern Tibetan Plateau - Hongfu Zhou; Meng Wang; Jingyi Xue; Rui Li; Jinpeng Hu; Jiang Xing; Tian Fang (Bulletin of Engineering Geology and the Environment, 2024)

A highly sensitive and colorimetric fluorescent probe for visualizing hydroxylamine in immune cells - Wei Du; Yang Tian; Yu-An Feng; Xiao-Wei Cong; Rui Tan; Ya-Wen Wang; Yu Peng (Analytica Chimica Acta, 2024)

An “off-on-enhanced on” electrochemiluminescence biosensor based on resonance energy transfer and surface plasmon coupled 3D DNA walker for ultra-sensitive detection of microRNA-21 - Meng-Li Li; Ming-Yu Zhong; Jia Zhang; Yi-Jia Zhang; Yu-Qi Zhang; Yan Liu; Xiang-Kai Li; Shu-Tian Gan; Gong-Rui Meng; Li Mi; Yong-Hong Hu; Fang Zhang; et al. (Analytica Chimica Acta, 2024)

A review of distribution and functions of extracellular DNA in the environment and wastewater treatment systems - Shaopo Wang; Ruimin Tian; Yanmeng Bi; Fansheng Meng; Rui Zhang; Chenchen Wang; Dong Wang; Lingjie Liu; Bo Zhang (Chemosphere, 2024)

Effect of volatile compounds produced by Weissella cibaria BWL4 on Botrytis cinerea infection in fruit and complete genome sequence analysis of BWL4 - Danfeng Zhang; Xuehua Xu; Xinrui Tian; Rui Wang; Tingting Hu; Wei Shi; Wanling Bi; Yingwang Ye (Postharvest Biology and Technology, 2024)

Different reference genomes determine different results: Comparing SNP calling in RAD-seq of Engelhardia roxburghiana using different reference genomes - Pei-Han Huang; Tian-Rui Wang; Min Li; Ou-Yan Fang; Ren-Ping Su; Hong-Hu Meng; Yi-Gang Song; Jie Li (Plant Science, 2024)

Qualitative classification of waste garments for textile recycling based on machine vision and attention mechanisms - Rui Tian; Ziqi Lv; Yuhan Fan; Tianyu Wang; Meijie Sun; Zhiqiang Xu (Waste Management, 2024)

Synergistic effects of Co-pyrolysis on the immobilization and transformation of lead (Pb), chromium (Cr), nickel (Ni), and fluorine (F) in phosphogypsum-biomass mixtures - Minjie He; Rui Xu; Guangfei Qu; Xianyu Fu; Xinxin Liu; Hanghang Wang; Yaxin Tian; Chenyang Yin (Journal of Environmental Management, 2024)

A randomised double-blind placebo-controlled trial of a probiotic combination for manipulating the gut microbiota and managing metabolic syndrome - Rui Xiao; Ying Chen; Xiaofeng Zhu; Linlin Wang; Peijun Tian; Xing Jin; Ming Liang; Zehua Chen; Ting Zhang; Long Qian; Qun Wang; Jianxin Zhao; et al. (Food Bioscience, 2024)

Stretchable ionogels: Recent advances in design, toughening mechanisms, material properties and wearable devices applications - Caiyue Huang; Xiaohua Jia; Ding Wang; Xisheng Sun; Qi Liang; Rui Tian; Liyuan Guo; Jin Yang; Haojie Song (Chemical Engineering Journal, 2024)

Efficient acidic CO2 electroreduction to formic acid by modulating electrode structure at industrial-level current - Zhenhui Wang; Hongdong Li; Tian Dong; Yanling Geng; Xiaofeng Tian; Rui Chang; Jianping Lai; Shouhua Feng; Lei Wang (Chemical Engineering Journal, 2024)

Establishment, characterization and application of Largemouth bronze gudgeon (Coreius guichenoti) fin and skin cell lines in disease resistance - Qi Zhang; Zhihong Gong; Rui Shi; Yuhong Shi; Chenfei Guo; Xiaolin Liao; Hua Tian; Na Wang (Aquaculture, 2024)

Assessing ammonium pollution and mitigation measures through a modified watershed non-point source model - Feng Han; Qing Tian; Nengwang Chen; Zhaoping Hu; Yao Wang; Rui Xiong; Peng Xu; Wei Liu; Alejandra Stehr; Ricardo O. Barra; Yi Zheng (Water Research, 2024)

Insights into the generation of multiple reactive species in UV254/PMS/I− system and their roles for degradation of phenolic and non-phenolic pollutants - Zhen Tian; Yiyang Li; Lina Wang; Rui Xu; Aihua Wei; Jun He; Chengjun Wang (Journal of Water Process Engineering, 2024)

Experimental study and model optimization of thermodynamic performance of a single screw water vapor compressor - Huafu Zhang; Zhentao Zhang; Lige Tong; Junling Yang; Yanan Li; Li Wang; Xia Guo; Rui Tian; Mingxin He; Chongguang Gao (International Journal of Refrigeration, 2024)

Constructing composite active centers optimized with Cr-doped NiS/NiS2 heterostructure for efficiently catalyzing alkaline hydrogen evolution reaction - Fanjia Sun; Xueqing Tian; Jianbing Zang; Rui Zhu; Zhiwei Hou; Youbin Zheng; Yanhui Wang; Liang Dong (Fuel, 2024)

Circular RNA MKLN1 promotes epithelial-mesenchymal transition in pulmonary fibrosis by regulating the miR-26a/b-5p/CDK8 axis in human alveolar epithelial cells and mice models - Yong Zhu; Xiaoxiao Meng; Xian Zhu; Jiaxiang Zhang; Hui lv; Feiyao Wang; Jinfeng Wang; Cheng Chen; Mengting Chen; Dapeng Wang; Wei Jin; Rui Tian; et al. (Archives of Toxicology, 2024)
Pulmonary fibrosis involves destruction of the lung parenchyma and extracellular matrix deposition. Effective treatments for pulmonary fibrosis are lacking and its pathogenesis is still unclear. Studies have found that epithelial-mesenchymal transition (EMT) of alveolar epithelial cells (AECs) plays an important role in progression of pulmonary fibrosis. Thus, an in-depth exploration of its mechanism might identify new therapeutic targets. In this study, we revealed that a novel circular RNA, MKLN1 (circMKLN1), was significantly elevated in two pulmonary fibrosis models (intraperitoneally with PQ, 50 mg/kg for 7 days, and intratracheally with BLM, 5 mg/kg for 28 days). Additionally, circMKLN1 was positively correlated with the severity of pulmonary fibrosis. Inhibition of circMKLN1 expression significantly reduced collagen deposition and inhibited EMT in AECs. EMT was aggravated after circMKLN1 overexpression in AECs. MiR-26a-5p/miR-26b-5p (miR-26a/b), the targets of circMKLN1, were confirmed by luciferase reporter assays. CircMKLN1 inhibition elevated miR-26a/b expression. Significantly decreased expression of CDK8 (one of the miR-26a/b targets) was observed after inhibition of circMKLN1. EMT was exacerbated again, and CDK8 expression was significantly increased after circMKLN1 inhibition and cotransfection of miR-26a/b inhibitors in AECs. Our research indicated that circMKLN1 promoted CDK8 expression through sponge adsorption of miR-26a/b, which regulates EMT and pulmonary fibrosis. This study provides a theoretical basis for finding new targets or biomarkers in pulmonary fibrosis.

ARHGEF18 can promote BVDV NS5B activation of the host NF-κB signaling pathway by combining with the NS5B-palm domain - Jiying Yin; Naichao Diao; Tian Tian; Qi Wang; Shuqi Ma; Ning He; Hongming Zhou; Zehui Zhou; Wenyi Jia; Xiaonan Wang; Kun Shi; Rui Du (Veterinary Microbiology, 2024)

DeepWMH: A deep learning tool for accurate white matter hyperintensity segmentation without requiring manual annotations for training - Chenghao Liu; Zhizheng Zhuo; Liying Qu; Ying Jin; Tiantian Hua; Jun Xu; Guirong Tan; Yuna Li; Yunyun Duan; Tingting Wang; Zaiqiang Zhang; Yanling Zhang; et al. (Science Bulletin, 2024)

Arbuscular mycorrhizal fungi reduce ammonia emissions under different land-use types in agro-pastoral areas - Huaisong WANG; Rui GUO; Yibo TIAN; Nan CUI; Xinxin WANG; Lei WANG; Zhongbao YANG; Shuying LI; Jixun GUO; Lianxuan SHI; Tao ZHANG (Pedosphere, 2024)

Fly ash-dominated High-Strength Engineered/Strain-Hardening Geopolymer Composites (HS-EGC/SHGC): Influence of alkalinity and environmental assessment - Jian-Cong Lao; Rui-Yang Ma; Ling-Yu Xu; Yang Li; Yi-Nong Shen; Jie Yao; Yan-Shuai Wang; Tian-Yu Xie; Bo-Tao Huang (Journal of Cleaner Production, 2024)

The isomorphous substitution of Si(4Al) with P in FAU zeolite and its stabilization effect - Qiang Zhang; Hongjuan Zhao; Xingyu Liu; Rui Li; Tian Xia; Yue Ma; Yuren Wang; Kang Chen; Jiujiang Wang; Penghui Zeng; Honghai Liu; Chaowei Liu; et al. (Chemical Engineering Journal, 2024)

Self-enhanced nanohydrogel electrochemiluminescence biosensor based on CRISPR/Cas12a and gold platinum nanoparticles modification for high-sensitivity detection of Burkholderia pseudomallei - Yuexin Wang; Bo Shen; Nini Luo; Cai Li; Haiping Wu; Yanshuang Wang; Shen Tian; Xuemiao Li; Rui Liu; Xinmin Li; Junman Chen; Wei Cheng; et al. (Chemical Engineering Journal, 2024)

Hollow AMn2O4-δ (A = Co, Zn, Ni) nanotube for direct photo-oxidation of methane to C1 and C2 alcohols at atmospheric pressure and room temperature - Jun Duan; Shiying Fan; Xinyong Li; Jing Wang; Chunpeng Bai; Shixuan Yu; Weitong Ling; Rui Tian; Dongke Zhang (Chemical Engineering Journal, 2024)

Impacts of an upper tropospheric cold low on the extreme precipitation in Henan Province, China in July 2021 - Liangliang Li; Wenshou Tian; Jian Li; Jinlong Huang; Rui Wang; Jiali Luo (Atmospheric Research, 2024)

Cement kiln geared up to dispose industrial hazardous wastes of megacity under industrial symbiosis - Kailingli Liao; Zeshi Feng; Jin Wu; He Liang; Yuhan Wang; Wenfei Zeng; Yichun Wang; Jinping Tian; Rui Liu; Lyujun Chen (Resources, Conservation and Recycling, 2024)

The transmission of isotopic signals from precipitation to groundwater and its controls: An experimental study with soil cylinders of various soil textures and burial depths in a monsoon region - Ying Jiang; Jie Li; Rui Zuo; Congjian Sun; Yuanzheng Zhai; Lijun Tian; Wei Dai; Shufang Wang; Ziqi Shang; Yulian Liu; Xuan Jiao; Yuxi Xie; et al. (Journal of Hydrology, 2024)

A high-affinity fluorescent probe for human uridine-disphosphate glucuronosyltransferase 1A9 function monitoring under environmental pollutant exposure - Yi-Sheng Miao; Jia-Yue Wang; Rui-Rui Zhuang; Xiao-Kui Huo; Zi-Chang Yi; Xiao-Nan Sun; Zhen-Long Yu; Xiang-Ge Tian; Jing Ning; Lei Feng; Xiao-Chi Ma; Xia Lv (Journal of Hazardous Materials, 2024)

Quantitative health risk assessment of microbial hazards from water sources for community and self-supply drinking water systems - Cheng Yan; Wei-di Wan; Rui-ning Wang; Tian-nuo Lai; Wajid Ali; Shan-shan He; Sai Liu; Xiang Li; Zaheer Ahmad Nasir; Frederic Coulon (Journal of Hazardous Materials, 2024)

The pH adjustment of Vitis amurensis dry red wine revealed the evolution of organic acids, volatomics, and sensory quality during winemaking - Meng-Bo Tian; Rui-Qi Hu; Zhao-Long Liu; Ning Shi; Hao-Cheng Lu; Chang-Qing Duan; Jun Wang; Yan-Feng Sun; Qing-Sen Kong; Fei He (Food Chemistry, 2024)

ZIF-8 Gel/PIM-1 mixed matrix membranes for enhanced H2/CH4 separations - Keming Zhang; Xianye Luo; Sihui Li; Xiaohe Tian; Qingnan Wang; Chenlu Liu; Yanting Tang; Xiaoting Feng; Rui Zhang; Shuangfeng Yin; Shaofei Wang (Chemical Engineering Journal, 2024)

Covalent-Metal organic Frameworks: Preparation and applications - Zhaobo Wang; Chen Wang; Qiming Hu; Xuefei Lei; Rui Guo; Junhua You; Ye Tian; Fan Yang; Meili Lv (Chemical Engineering Journal, 2024)

A particle-scale insight into the face stability of shallow EPB shield tunnels in dry cobble-rich soil - Jun Wang; Guojin Lin; Rui Tang; Yan Zhang; Zhigang Yao; Kun Feng; Ning Tian; Ziquan Chen; Chuan He (Tunnelling and Underground Space Technology, 2024)

Long-term MNNG exposure promotes gastric carcinogenesis by activating METTL3/m6A/miR1184 axis-mediated epithelial-mesenchymal transition - Tong Liu; Yan-lu Feng; Rui-ying Wang; Sheng Yang; Yi-ling Ge; Tian-yi Zhang; Jie Li; Cheng-yun Li; Ye Ruan; Bin Luo; Ge-yu Liang (Science of The Total Environment, 2024)

Molecular epidemiology, phenotypic and genomic characterization of antibiotic-resistant enterococcal isolates from diverse farm animals in Xinjiang, China - Wanzhao Chen; Qiaojun Wang; Huimin Wu; Panpan Xia; Rui Tian; Ruichao Li; Lining Xia (Science of The Total Environment, 2024)

Vapor-liquid equilibrium measurement for carbon dioxide (CO2)+propylene (R1270) binary mixture at temperatures from subcritical to supercritical - Zirui Wu; Rui Sun; Lingfeng Shi; Peng Hu; Hua Tian; Xuan Wang; Gequn Shu (International Journal of Refrigeration, 2024)

Involvement of TLRs/NF-κB/ESE-1 signaling pathway in T-2 toxin-induced cartilage matrix degradation - Yawen Shi; Rui Wang; Yanan Li; Yixin Cui; Ying He; Hui Wang; Yinan Liu; Meng Zhang; Yonghui Chen; Mingzhao Jia; Kunpan Chen; Xingran Ruan; et al. (Environmental Pollution, 2024)

Estimation of water quality variables based on machine learning model and cluster analysis-based empirical model using multi-source remote sensing data in inland reservoirs, South China - Di Tian; Xinfeng Zhao; Lei Gao; Zuobing Liang; Zaizhi Yang; Pengcheng Zhang; Qirui Wu; Kun Ren; Rui Li; Chenchen Yang; Shaoheng Li; Meng Wang; et al. (Environmental Pollution, 2024)

Function-oriented bifunctional Mg & MoP modified polymeric carbon nitride for selective photoreduction CO2 to CH4 - Jun-ying Tang; Wei-guo Pan; Yu-lian He; Tian-shuo Zhao; Qing-shan Wang; Rui-tang Guo (Chemical Engineering Journal, 2024)

Short-term exposure to ambient air pollution and hospital admissions for angina among older adults in South China - Luxi Xu; Ruijun Xu; Yunshao Ye; Rui Wang; Jing Wei; Chunxiang Shi; Qiaoxuan Lin; Ziquan Lv; Suli Huang; Qi Tian; Yuewei Liu (Atmospheric Environment, 2024)

New 4',5'-methylenedioxyflavone derivatives from the whole plant of sarcandra glabra - Ya-Qiu Qin; Wei Liu; Rui Yin; Ping-Ting Xiao; Zi-Yuan Wang; Tian-Qing Huang; E-Hu Liu (Natural Product Research, 2024)

Stytontriterpenes A−C, three unusual oleanane-derived triterpenoids from the resin of Styrax tonkinensis as potential immunosuppressive agents in atherosclerosis - Rui-Yan Jiang; Ling-Wen Yao; Yin-Hong Lv; Zhong-Tian Guo; Fei-Fei Wang; Hong-Hua Cui; Yuan-Yuan Cheng; Feng Wang (Phytochemistry, 2024)

A review of the strategy to promote microalgae value in CO2 conversion-lipid enrichment-biodiesel production - Huan Liu; Tian-Ji Liu; Hua-Wei Guo; Ya-Jun Wang; Rui Ji; Le-Le Kang; Yi-Tong Wang; Xuan Guo; Jun-Guo Li; Li-Qun Jiang; Zhen Fang (Journal of Cleaner Production, 2024)

LED-driven photocatalytic degradation of tetracycline by chromite ore processing residue (COPR): Mechanism, pathway, toxicity assessment - Shuo Zhang; Cunfang Lu; Yelei Wang; Cheng Tian; Peng Chen; Mingyuan Yang; Min Zhang; Rui Xu; Yuanyuan He; Zilong Li (Journal of Cleaner Production, 2024)

Fluid evolution and gas enrichment in the Wufeng-Longmaxi shale reservoirs of the eastern Sichuan Basin, SW China - Tao Luo; Xiaowen Guo; Zhiliang He; Tian Dong; Ze Tao; Rui Yang; Keqing Wang (Journal of Asian Earth Sciences, 2024)

A portable on-demand therapeutic nitric oxide generation apparatus: New strategy for diabetic foot ulcers - Huihui Bian; Junjie Wang; Xiaodong Shan; Xiuqing Li; Yongjin Wang; Rui Sun; Chongxian Wang; Juan Lv; Chunlei Xing; Chunlei Hui; Dinglei Zhang; Chenxi Zhang; et al. (Chemical Engineering Journal, 2024)

Ultra-stretchable, sensitive and breathable electronic skin based on TPU electrospinning fibrous membrane with microcrack structure for human motion monitoring and self-powered application - Yu Tian; Mengjie Huang; Yalong Wang; Yanjun Zheng; Rui Yin; Hu Liu; Chuntai Liu; Changyu Shen (Chemical Engineering Journal, 2024)

Sulfite activation of Fe-Mn bimetallic oxides for rapid oxidative removal of As(III) in water: Involvement of active Mn(III) - Guiyuan Cai; Yu Tian; Lipin Li; Wenxuan Zhang; Rui Huang; Jun Zhang; Qinyu Wang; Hua Xu; Yifeng Zhang (Chemical Engineering Journal, 2024)

Effect of vane angle on turbulence–chemistry interactions, temperature, flow field, burnout, and NOx emissions in swirling flames fueled by semicoke mixtures - Liutao Sun; Shengyu Kuang; Weilin Li; Jingjie Wang; Yanhui Xu; Lingkun Zhu; Hong Tian; Xinzhuo Li; Dengke Wang; Rui Sun (Environmental Science and Pollution Research, 2023)

The co-regulation of the gut microbiome and host genes might play essential roles in metformin gastrointestinal intolerance - Huixiang Zhang; Jiao Lai; Lihuan Zhang; Wei Zhang; Xun Liu; Qilin Gong; Hongxi Tian; Mingzhi Yang; Tao Yang; Rui Zhao; Dongqing Li; Hehua Huang; et al. (Toxicology and Applied Pharmacology, 2023)

Nanoplastic-Induced Biological Effects In Vivo and In Vitro: An Overview - Hongxin Xie; Xue Tian; Xiaoying Lin; Rui Chen; Saima Hameed; Liming Wang; Yong-Liang Yu; Bai Li; Yu-Feng Li (Reviews of Environmental Contamination and Toxicology, 2023)

Insights of microalgal municipal wastewater treatment at low temperatures: Performance, microbiota patterns, and cold-adaptation of tubular and aeration column photobioreactors - Jiansong Tian; Pan Li; Yajun Luo; Heng Yan; Jian Liu; Zhicheng Pan; Yangwu Chen; Rui Wang; Yiwei Cheng; Houzhen Zhou; Junjie Li; Xin Li; et al. (Chemosphere, 2023)

A novel method of desynchronized operation of sails for ship wind-assisted propulsion system - Rui Zhang; Lianzhong Huang; Guisheng Peng; Ranqi Ma; Kai Wang; Feng Tian; Qiushi Song (Ocean Engineering, 2023)

Experimental study on enhanced coal seam gas extraction by uniform pressure/pulse pressure N2 injection - Peng-fei Ji; Hai-fei Lin; Xiang-guo Kong; Shu-gang Li; Yu-chu Cai; Rui-zhe Wang; Yu Tian; Tian-shuo Zhao (Fuel, 2023)

A review of the toxic effects of ammonia on invertebrates in aquatic environments - Tian-Xu Zhang; Ming-Rui Li; Chen Liu; Shu-Ping Wang; Zhen-Guang Yan (Environmental Pollution, 2023)

Early clues and molecular mechanism involved in neurodegenerative diseases induced in immature mice by combined exposure to polypropylene microplastics and DEHP - Ge Yang; Cunyi Gong; Xinyue Zheng; Fei Hu; Jie Liu; Tian Wang; Xinyue Chen; Min Li; Zhihong Zhu; Ling Zhang; Rui Li (Environmental Pollution, 2023)

Comprehensive properties of non-penetrating and penetrating deep convection precipitation in summer over the Tibetan Plateau derived from GPM observations - Rui Wang; Zhongshan Jiang; Fengjiao Chen; Wenshou Tian; Liangliang Li; Hongying Tian; Jiali Luo (Atmospheric Research, 2023)

A new anchor-siphon drainage combined method used for slope stabilization - Hong-yue Sun; Xu Wang; Yang Yu; Jun-wei Shu; Tian-long Wang; Rui Luo; Zhao-wei Chu (Journal of Mountain Science, 2023)

Triterpenoid saponins from Psammosilene tunicoides and their antinociceptive activities - Yan-Hong Li; Xi-Shan Bai; Xiu-Xia Yang; Yu-Xiao Li; Hong-Rui Li; Zi-Liang Wang; Wei Wang; Kai Tian; Xiang-Zhong Huang (Phytochemistry, 2023)

Characterization of a gE/gI/TK gene-deleted pseudorabies virus variant expressing the Cap protein of porcine circovirus type 2d - Rui-Qin Xu; Lin-Qing Wang; Hui-Hua Zheng; Run-Bo Tian; Lan-Lan Zheng; Shi-Jie Ma; Hong-Ying Chen (Comparative Immunology, Microbiology and Infectious Diseases, 2023)

QSPR models for sublimation enthalpy of energetic compounds - Rui Liu; Yuechuan Tang; Jie Tian; Jing Huang; Chaoyang Zhang; Linyuan Wang; Jian Liu (Chemical Engineering Journal, 2023)

Anti-ice-pinning superhydrophobic surfaces for extremely low ice adhesion - Ze Tian; Peixun Fan; Dongyu Zhu; Lizhong Wang; Huanyu Zhao; Changhao Chen; Rui Peng; Daizhou Li; Hongjun Zhang; Minlin Zhong (Chemical Engineering Journal, 2023)

Integrative analyses of RNA-seq and ChIP-seq Reveal MITF as a Target Gene of TFPI-2 in MDA231 Cells - Guangli Wang; Gaofeng Zhang; Ningxia Zhu; Chunjiang Zhu; Mafei Kang; Guidan Zuo; Zhijie Niu; Wei Ye; Baodong Tian; Rui Cai (Biochemical Genetics, 2023)

Effects of atrazine on microbial metabolic limitations in black soils: Evidence from enzyme stoichiometry - Tiancong Gao; Haixia Tian; Ziqi Wang; Jing Shi; Rui Yang; Fang Wang; Leilei Xiang; Yunchao Dai; Mallavarapu Megharaj; Wenxiang He (Chemosphere, 2023)

Farmers’ participation into the recovery of waste agricultural plastic film: An application of the Theory of Planned Behavior - Ze-Ying Zhao; Wen-Bo Li; Peng-Yang Wang; Hong-Yan Tao; Rui Zhou; Jin-Ying Cui; Jian Zhang; Tao Tian; Xu-Zhe Zhao; Yi-Bo Wang; You-Cai Xiong (Waste Management, 2023)

Nitrate attenuation with rising groundwater levels: An integrated assessment using isotope tracers and microbial signatures - Jie Li; Yulian Liu; Wei Dai; Jian Li; Pingheng Yang; Lijun Tian; Shihang Yu; Rui Zuo; Yuanzheng Zhai; Wei Song; Fan Yang; Ruijing Zhou; et al. (Journal of Hydrology, 2023)

Achieving reasonable waste heat utilization in all truck operating conditions via a dual-pressure organic rankine cycle and its operating strategy - Xuanang Zhang; Xuan Wang; Jinwen Cai; Rui Wang; Xingyan Bian; Ping Yuan; Hua Tian; Gequn Shu (Journal of Cleaner Production, 2023)

Regeneration of high-performance materials for electrochemical energy storage from assorted solid waste: A review - Jia-feng Zhang; De-zhao Peng; Xiang-gang Gao; Jing-tian Zou; Long Ye; Guan-jun Ji; Bi Luo; Gui-hui Yu; Peng-fei Li; Xiao-wei Wang; Zao-wen Zhao; Bao Zhang; et al. (Journal of Cleaner Production, 2023)

Comprehensive understanding of tetracycline hydrochloride adsorption mechanism onto biochar-based gel pellets based on the combination of characterization-based and approximate site energy distribution methods - Bai-Qin Zhou; Qian-Qian Sang; Yu-Jun Wang; Hui Huang; Fang-Jun Wang; Rui-Chun Yang; Yuan-Tian Zhao; Zi-Jie Xiao; Chun-Yue Zhang; Hui-Ping Li (Journal of Cleaner Production, 2023)

Generation of gridded temperature map of constant-temperature layer based on meteorological data for shallow geothermal applications - Rui Mao; Zilong Zhao; Lei Tian; Tiantian Fang; Xinlei Wang (Geothermics, 2023)

Expression and functional analysis of ace1 and ace2 reveal their differential roles in larval growth and insecticide sensitivity in Spodoptera frugiperda (J. E. Smith, 1797) - Jie Gao; Li-Feng Gong; Huan-Huan Wang; Rui Zhao; Xing Xiao; Xin-Yao Tian; Bo Li; Pei Liang; Xi-Wu Gao; Shao-Hua Gu (Journal of Pest Science, 2023)

Moringa oleifera Lam. leaves as new raw food material: A review of its nutritional composition, functional properties, and comprehensive application - Min Yang; Liang Tao; Xin-Rui Kang; Zi-Lin Wang; Ling-Yan Su; Ling-Fei Li; Fan Gu; Cun-Chao Zhao; Jun Sheng; Yang Tian (Trends in Food Science & Technology, 2023)

Efficient lipid synthesis of Chlorella pyrenoidosa promoted under heavy metals from electric arc furnace slag - Qing Yu; Tian-Ji Liu; Ya-Nan Zeng; Yi-Tong Wang; Jun-Guo Li; Yu-Ran Wang; Le-Le Kang; Rui Ji; Fu-Ping Wang; Xiao-Man Wang; Bao Liu; Shuang Cai; et al. (Journal of Cleaner Production, 2023)

Machine learning improves prediction of severity and outcomes of acute pancreatitis: a prospective multi-center cohort study - Jia-Ning Li; Dong Mu; Shi-Cheng Zheng; Wei Tian; Zuo-Yan Wu; Jie Meng; Rui-Feng Wang; Tian-Lei Zheng; Yue-Lun Zhang; John Windsor; Guo-Tao Lu; Dong Wu (Science China Life Sciences, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

The PIWI-specific insertion module helps load longer piRNAs for translational activation essential for male fertility - Xin Wang; Di-Hang Lin; Yue Yan; An-Hui Wang; Jiaoyang Liao; Qian Meng; Wen-Qing Yang; Heng Zuo; Min-Min Hua; Fengjuan Zhang; Hongwen Zhu; Hu Zhou; et al. (Science China Life Sciences, 2023)

Developing practical and small-scale radio frequency technology for tempering minced chicken breast at home - Yingqi Tian; Mengge Li; Xiangyu Guan; Rui Li; Hosahalli Ramaswamy; Shaojin Wang (Innovative Food Science & Emerging Technologies, 2023)

Internet addiction-induced brain structure and function alterations: a systematic review and meta-analysis of voxel-based morphometry and resting-state functional connectivity studies - Jing-Ting Sun; Bo Hu; Tian-Qi Chen; Zhu-Hong Chen; Yu-Xuan Shang; Yu-Ting Li; Rui Wang; Wen Wang (Brain Imaging and Behavior, 2023)

High-resolution records of sea surface temperature and salinity in the East China Sea over the past 14.2 kyr: Implication from alkenone and its hydrogen isotopes - Rui Zhang; Wenlong Pei; Yipeng Wang; Xinling Wang; Jiayue Wang; Tiegang Li; James Russell; Fan Zhang; Zhiyong Liu; Minglei Guan; Qi Han; Chenyang Tian; et al. (Global and Planetary Change, 2023)

Structural incorporation of iron influences biomethylation potential of mercury sulfide - Yunyun Ji; Shan Gao; Rui Si; Zhanhua Zhang; Li Tian; Wenyu Guan; Weichao Wang; Jiubin Chen; Wei Chen; Pedro J.J. Alvarez; Tong Zhang (Geochimica et Cosmochimica Acta, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Estimating the maximum vegetation coverage and productivity capacity supported by rainwater resources on the Loess Plateau - Yao Li; Baoqing Zhang; Rui Shao; Tongxuan Su; Xuejin Wang; Lei Tian; Chansheng He (Journal of Hydrology, 2023)

A critical review on graphene oxide membrane for industrial wastewater treatment - Ye-Chen An; Xiao-Xu Gao; Wen-Li Jiang; Jing-Long Han; Yuan Ye; Tian-Ming Chen; Rui-Yun Ren; Jia-Hui Zhang; Bin Liang; Zhi-Ling Li; Ai-Jie Wang; Nan-Qi Ren (Environmental Research, 2023)

Polycyclic aromatic hydrocarbon exposure burden: Individual and mixture analyses of associations with chronic obstructive pulmonary disease risk - Kun Peng; Zhao Li; Tian-Rui Gao; Jia Lv; Wen-Jing Wang; Ping Zhan; Wen-Cong Yao; Hui Zhao; Hua Wang; De-Xiang Xu; Yichao Huang; Zhu-Xia Tan (Environmental Research, 2023)

An ultra-thin chemical vapor deposited polymer interlayer to achieve highly improved stability of perovskite solar cell - Jing Zhou; Xueying Tian; Rui Chen; Weitao Chen; Xin Meng; Xinyu Guan; Jianan Wang; Sanwan Liu; Fumeng Ren; Shasha Zhang; Yiqiang Zhang; Zonghao Liu; et al. (Chemical Engineering Journal, 2023)

Magnetic hydrochar derived from waste lignin for thallium removal from wastewater: Performance and mechanisms - Huabin Wang; Ran Duan; Lin Ding; Lin Tian; Ying Liu; Yong Zhang; Rui Xu (Bioresource Technology, 2023)

Co-cultivation of microalgae-activated sludge for municipal wastewater treatment: Exploring the performance, microbial co-occurrence patterns, microbiota dynamics and function during the startup stage - Xin Li; Jian Liu; Jiansong Tian; Zhicheng Pan; Yangwu Chen; Fei Ming; Rui Wang; Lin Wang; Houzhen Zhou; Junjie Li; Zhouliang Tan (Bioresource Technology, 2023)

Reduced plastic film mulching under zero tillage boosts water use efficiency and soil health in semiarid rainfed maize field - Ai-Tian Ren; Ji-Yuan Li; Ling Zhao; Rui Zhou; Jian-Sheng Ye; Yi-Bo Wang; Xu-Cheng Zhang; Kiprotich Wesly; Ming-Sheng Ma; You-Cai Xiong (Resources, Conservation and Recycling, 2023)

Exploring the heterogeneity in drivers of energy-saving behaviours among hotel guests: Insights from the theory of planned behaviour and personality profiles - Qian-Cheng Wang; Yi-Tian Ren; Xuan Liu; Rui-Dong Chang; Jian Zuo (Environmental Impact Assessment Review, 2023)

Ultrasensitive hydrogel grating detector for real-time continuous-flow detection of trace threat Pb2+ - Xiao-Yu Tian; Meng-Wei Sun; Guo-Yu Wen; Min Cao; Da-Wei Pan; Rui Xie; Xiao-Jie Ju; Zhuang Liu; Wei Wang; Liang-Yin Chu (Journal of Hazardous Materials, 2023)

Antimicrobial activity and mechanism of preservatives against Alicyclobacillus acidoterrestris and its application in apple juice - Zhouli Wang; Yu Tian; Qi Wang; Tianmin Guo; Yahong Yuan; Tianli Yue; Hang Jia; Qian Ge; Zidan Zhao; Rui Cai (International Journal of Food Microbiology, 2023)

Metagenomic insights into bacterial communities and functional genes associated with texture characteristics of Kazakh artisanal fermented milk Ayran in Xinjiang, China - Malina Kuerman; Rui Wang; Yu Zhou; Xiaoying Tian; Qingyu Cui; Huaxi Yi; Pimin Gong; Zhe Zhang; Kai Lin; Tongjie Liu; Lanwei Zhang (Food Research International, 2023)

Paenibacillus alkalitolerans sp. nov., a bacterium isolated from a salt lake of Turpan City in Xinjiang Province, north-west China - Rui Li; Zhou-Tian-Le Zhang; Yun Wang; Gang-Qiang Jiang; Min Yin; Yu Li; Wen-Yong Zhu; Shu-Kun Tang (Folia Microbiologica, 2023)

HIF-1α promotes paraquat induced acute lung injury and implicates a role NF-κB and Rac2 activity - Yong Zhu; Xiaoxiao Meng; Wenyu Yang; Jinfeng Wang; Jiaxiang Zhang; Rui Tian; Ruilan Wang; Qi Su; Wei Jin (Toxicology, 2023)

The formation of supercritical carbon dioxide hydrothermal vents in the Okinawa Trough - Fanfan Tian; Rui Li; Guozhi Xie; Kun Wang; Lipeng Zhang; Xin Zhang; Weidong Sun (Science Bulletin, 2023)

Evaluating performances of a small-scale 50 Ω radio frequency heating system designed for home applications - Yingqi Tian; Xiangyu Guan; Rui Li; Hosahalli Ramaswamy; Shaojin Wang (Innovative Food Science & Emerging Technologies, 2023)

Janus fibrous membrane with directional liquid transport capacity for wound healing promotion - Haohong Pi; Yanli Xi; Jing Wu; Miaomiao Hu; Boyang Tian; Yiwen Yang; Rui Wang; Xiuqin Zhang (Chemical Engineering Journal, 2023)

All-in-one additive enables defect passivated, crystallization modulated and moisture resisted perovskite films toward efficient solar cells - Chuanming Tian; Yu Zhao; Xuefei Han; Bin Li; Yichuan Rui; Hao Xiong; Yu Qiu; Wei An; Kerui Li; Chengyi Hou; Yaogang Li; Hongzhi Wang; et al. (Chemical Engineering Journal, 2023)

Yeast cell wall polysaccharides in Tibetan kefir grains are key substances promoting the formation of bacterial biofilm - XiaoMeng Wang; XueLiang Zhang; YuKe Wang; NanYu Tang; LuYao Xiao; JuanJuan Tian; Xin Rui; Wei Li (Carbohydrate Polymers, 2023)

Solar ring mission: Building a panorama of the Sun and inner-heliosphere - Yuming Wang; Xianyong Bai; Changyong Chen; Linjie Chen; Xin Cheng; Lei Deng; Linhua Deng; Yuanyong Deng; Li Feng; Tingyu Gou; Jingnan Guo; Yang Guo; et al. (Advances in Space Research, 2023)

Leakage Fault Diagnosis of Lifting and Lowering Hydraulic System of Wing-Assisted Ships Based on WPT-SVM - Ranqi Ma; Haoyang Zhao; Kai Wang; Rui Zhang; Yu Hua; Baoshen Jiang; Feng Tian; Zhang Ruan; Hao Wang; Lianzhong Huang (Journal of Marine Science and Engineering, 2022)
Wing-assisted technology is an effective way to reduce emissions and promote the decarbonization of the shipping industry. The lifting and lowering of wing-sail is usually driven by hydraulic system. Leakage, as an important failure form, directly affects the safety as well as the functioning of hydraulic system. To increase the system reliability and improve the wing-assisted effect, it is essential to conduct leakage fault diagnosis of lifting and lowering hydraulic system. In this paper, an AMESim simulation model of lifting and lowering hydraulic system of a Very Large Crude Carrier (VLCC) is established to analyze the operation characteristics of the hydraulic system. The effectiveness of the model is verified by the operation data of the actual hydraulic system. On this basis, a wavelet packet transform (WPT)-based sensitive feature extracting method of leakage fault for the hydraulic system is proposed. Subsequently, a support vector machine (SVM)-based multi-classification model and diagnosis method of leakage fault are proposed. The study results show that the proposed method has an accuracy of as high as 97.5% for six leakage fault modes. It is of great significance for ensuring the reliability of the wing-sail operation and improving the utilization rate of the offshore wind resources.

Efficacy and Safety of Recombinant Human Prourokinase in Acute Ischemic Stroke: A Phase IIa Randomized Clinical Trial - Haiqing Song; Yuan Wang; Qingfeng Ma; Huisheng Chen; Bo Liu; Yi Yang; Jianguo Zhu; Shigang Zhao; Xiaoping Jin; Yongqiu Li; Yanyong Wang; Runxiu Zhu; et al. (Translational Stroke Research, 2022)

GITRL impairs the immunosuppressive function of MDSCs via PTEN-mediated signaling pathway in experimental Sjögren syndrome - Jie Tian; Beibei Zhang; Qingfang Yuan; Xueqing Sun; Na Peng; Bo Zhu; Chang Liu; Xiaoran Wang; Man Han; Meng Cao; Fan Xiao; Shengjun Wang; et al. (Inflammation Research, 2022)

MicroRNA alteration in cerebrospinal fluid from comatose patients with traumatic brain injury after right median nerve stimulation - Ying Jia; Yi-fan He; Ye Tian; Yuan-zhi Wang; Rui-ting Zhao; Xiao-chun Li; Jian Sun; Ying-sheng Wei; Shuo An; Heng-jie Yuan; Chun-xiao Wan; Rong-cai Jiang (Experimental Brain Research, 2022)

Research on PEMS Test Data Processing Method and Cold Start Emission Evaluation Method of Heavy-Duty Diesel Vehicles - Gangzhi Tang; Shuaibin Wang; Rui Wang; Baocheng Du; Yu Liu; Gang Tian; Linyao Ran; Gan Xiang; Huang Li (Water, Air, & Soil Pollution, 2022)

Magnetic Resonance Imaging Markers of Cerebral Small Vessel Disease in Adults with Moyamoya Disease - Haogeng Sun; Wanjiang Li; Chao Xia; Yutao Ren; Lu Ma; Anqi Xiao; Chao You; Xiaoyu Wang; Rui Tian; Yi Liu (Translational Stroke Research, 2022)

Plant-mediated rhizospheric interactions in rice and water spinach intercropping enhance Si uptake by rice - Chuanchuan Ning; Lei Wang; Rui Liu; Taowen Pan; Yixia Cai; Jihui Tian; Shiming Luo; Kunzheng Cai (Plant and Soil, 2022)

Homocysteine-Induced Disturbances in DNA Methylation Contribute to Development of Stress-Associated Cognitive Decline in Rats - Shi-Da Wang; Xue Wang; Yun Zhao; Bing-Hua Xue; Xiao-Tian Wang; Yu-Xin Chen; Zi-Qian Zhang; Ying-Rui Tian; Fang Xie; Ling-Jia Qian (Neuroscience Bulletin, 2022)

Sandstorms cause shrinkage of Haloxylon ammodendron shrubs and limit their self-renewal - Sheng-bo Shi; Dang-wei Zhou; Fang-lin Wang; Rui Shi; Tao Sun; Tian-cai Li; Jia-lin Ma; Xiang Wan; Jian-ping Ma; Jing-nian Tang (Theoretical and Experimental Plant Physiology, 2022)
Haloxylon ammodendron is an excellent windproof and sand-fixing species whose shrubs are widely cultivated in arid desert areas of northwest China but are now at risk of degradation and shrinkage. Using the chlorophyll fluorescence image analysis technique, the response of photosystem II (PSII) photochemical efficiency and non-photochemical quenching capacity to sediment-carrying wind and sand-free wind (both 12 m s −1 ) lasting for 10, 20, and 40 min were studied with seedlings in a wind tunnel. The results indicated that the sand-free wind had little influence on the maximum quantum efficiency of PSII photochemistry, F v / F m , which was approximately 0.80 on average; however, the F v / F m decreased over exposure time in the sediment-carrying wind group, with values smaller than those in the wind-only group. The non-photochemical quenching was sensitive to wind erosion, and sediment-carrying wind could aggravate the reduction in non-photochemical quenching ( NPQ ). Except for the 10 min duration, the maximum quantum efficiency of PSII photochemistry after dark recovery for 15 min, F v r / F m r , was lower in seedlings exposed to sediment-carrying wind than in those in the wind-only group. Compared to wind-only, wind-blown sand led to a water imbalance and withering in seedlings, causing the concentration of photosynthetic pigments (when based on the fresh mass of green branches) to not decrease. With a longer exposure time to sediment-carrying wind, both the probability and extent of lignified spots occurring increased in green assimilative branches. Our results demonstrated that sediment-carrying wind at 12 m s −1 lasting for 20 min or more could cause irreversible damage to the photosynthetic apparatus of H. ammodendron seedlings. Therefore, frequent and strong sandstorms are the main disturbance factors leading to shrinkage of shrubs and limiting their self-renewal.

The interplay of particle properties and solution chemistry on aggregation kinetics of soil nanoparticles - Ning Hu; Chen-yang Xu; Zeng-chao Geng; Fei-nan Hu; Qi-rui Li; Ren-tian Ma; Qiang Wang (Journal of Soils and Sediments, 2022)

Toxic encephalopathy induced by radix Sophorae tonkinensis - Xue-Lin Li; Hao-Tian Zhao; Jinming Han; Zhong-Rui Yan; Hai-Yang Wang (Acta Neurologica Belgica, 2022)

Application of nanostructures as antimicrobials in the control of foodborne pathogen - Yu Tian; Rui Cai; Tianli Yue; Zhenpeng Gao; Yahong Yuan; Zhouli Wang (Critical Reviews in Food Science and Nutrition, 2022)

Chrysomutanin and related meroterpenoids from a DES mutant of the marine-derived fungus Penicillium chrysogenum S-3-25 - Hua Qiao; Shu-Hua Zhang; Yuan Dong; Yu Yang; Rui Xu; Bo Chen; Yi Wang; Tian-Jiao Zhu; Cheng-Bin Cui; Guo-Gang Zhang; Chang-Wei Li (Natural Product Research, 2022)

Positron Emission Tomography Molecular Imaging for Phenotyping and Management of Lymphoma - Xiaohui Zhang; Han Jiang; Shuang Wu; Jing Wang; Rui Zhou; Xuexin He; Shufang Qian; Shuilin Zhao; Hong Zhang; Ali Cahid Civelek; Mei Tian (Phenomics, 2022)

Dysfunction of FadA‐cAMP signalling decreases Aspergillus flavus resistance to antimicrobial natural preservative Perillaldehyde and AFB1 biosynthesis - Kunlong Yang; Qingru Geng; Yue Luo; Rui Xie; Tongzheng Sun; Zhen Wang; Ling Qin; Wei Zhao; Man Liu; Yongxin Li; Jun Tian (Environmental Microbiology, 2022)
Summary Aspergillus flavus is an opportunistic fungal pathogen that colonizes agriculture crops with aflatoxin contamination. We found that Perillaldehyde (PAE) effectively inhibited A . flavus viability and aflatoxin production by inducing excess reactive oxygen species (ROS). Transcriptome analysis indicated that the Gα protein FadA was significantly induced by PAE. Functional characterization of FadA showed it is important for asexual development and aflatoxin biosynthesis by regulation of cAMP‐PKA signalling. The Δ fadA mutant was more sensitive to PAE, while Δ pdeL and Δ pdeH mutants can tolerate excess PAE compared to wild‐type A . flavus . Further RNA‐sequence analysis showed that fadA was important for expression of genes involved in oxidation–reduction and cellular metabolism. The flow cytometry and fluorescence microscopy demonstrated that Δ fadA accumulated more concentration of ROS in cells, and the transcriptome data indicated that genes involved in ROS scavenging were downregulated in Δ fadA mutant. We further found that FadA participated in regulating response to extracellular environmental stresses by increasing phosphorylation levels of MAPK Kinase Slt2 and Hog1. Overall, our results indicated that FadA signalling engages in mycotoxin production and A . flavus resistance to antimicrobial PAE, which provide valuable information for controlling this fungus and AF biosynthesis in pre‐ and postharvest of agricultural crops.

Secondary metabolites isolated from Agrimonia pilosa Ledeb. - Hong-Rui Li; Yu-Kui Li; Jian Xiao; Cui Yang; Meng-Yuan Jiang; Kai Tian; Wei Wang; Yan-Hong Li; Xiang-Zhong Huang (Natural Product Research, 2022)

Qaidamihabitans albus gen. nov., sp. nov., a new member of the family Pseudonocardiaceae, and transfer of Prauserella shujinwangii to Qaidamihabitans gen. nov. as Qaidamihabitans shujinwangii comb. nov. - Li-Sha Tian; Gang-Qiang Jiang; Rui Li; Ping Ni; Chuan-En Li; Hong-Yan Zhang; Juan Wang; Xiao-Ping Zhang; Yun Wang; Shu-Kun Tang (Archives of Microbiology, 2021)

Genetic control of Fusarium head blight resistance in two Yangmai 158-derived recombinant inbred line populations - Haisheng Yan; Guoqiang Li; Jinxing Shi; ShunShun Tian; Xiaoqiu Zhang; Rui Cheng; Xin Wang; Yang Yuan; Shouyang Cao; Jiyang Zhou; Zhongxin Kong; Haiyan Jia; et al. (Theoretical and Applied Genetics, 2021)

Oxiracetam Mediates Neuroprotection Through the Regulation of Microglia Under Hypoxia-Ischemia Neonatal Brain Injury in Mice - Dan Wang; Yanbang Wei; Jingxia Tian; Dong He; Rui Zhang; Xiaoshuai Ji; Xiaoming Huang; Jun Sun; Jiajia Gao; Zixiao Wang; Qi Pang; Qian Liu (Molecular Neurobiology, 2021)

Gradually evaluating of suicidal risk in depression by semi-supervised cluster analysis on resting-state fMRI - Zhongpeng Dai; Xiangyu Shen; Shui Tian; Rui Yan; Huan Wang; Xinyi Wang; ZhiJian Yao; Qing Lu (Brain Imaging and Behavior, 2021)

A functional chromogen gene C from wild rice is involved in a different anthocyanin biosynthesis pathway in indica and japonica - Weihua Qiao; Yanyan Wang; Rui Xu; Ziyi Yang; Yan Sun; Long Su; Lizhen Zhang; Junrui Wang; Jingfen Huang; Xiaoming Zheng; Shijia Liu; Yunlu Tian; et al. (Theoretical and Applied Genetics, 2021)

Leaf Transcriptome and Weight Gene Co-expression Network Analysis Uncovers Genes Associated with Photosynthetic Efficiency in Camellia oleifera - Zhilong He; Caixia Liu; Xiangnan Wang; Rui Wang; Yun Tian; Yongzhong Chen (Biochemical Genetics, 2021)

Heteroaggregation of humic acid with montmorillonite in divalent electrolytes: effects of humic acid content and ionic concentration - Xiaodan Gao; Yingde Xu; Zhongyi Li; Song Li; Rui Tian; Hang Li; Rattan Lal; Lingzhi Liu; Muhammad Farhan Saeed; Jingkuan Wang (Journal of Soils and Sediments, 2021)

Small RNA Sequencing Analysis of Germinating Single-bud Seedcane Sett in Sugarcane - Kai-Chao Wu; Lin Xu; Zhi-Nian Deng; Tian Pang; Rong-Hua Zhang; Yi-Jie Li; Xiao-Yan Liu; Cheng-Feng Huang; Wen-Xian Qin; Jian-Feng Wei; Li-Ping Wei; Yang-Rui Li; et al. (Sugar Tech, 2021)

Astrocyte-Derived Lactate Modulates the Passive Coping Response to Behavioral Challenge in Male Mice - Ya-Nan Yin; Jian Hu; Yi-Li Wei; Ze-Lin Li; Zhou-Cai Luo; Rui-Qi Wang; Ke-Xin Yang; Shu-Ji Li; Xiao-Wen Li; Jian-Ming Yang; Tian-Ming Gao (Neuroscience Bulletin, 2021)

CD49a+CD49b+ NK cells induced by viral infection reflect an activated state of conventional NK cells - Wenhan Li; Jing Zhou; Xianwei Wang; Yuzhang Wu; Lilin Ye; Haiming Wei; Rui Sun; Zhigang Tian; Hui Peng (Science China Life Sciences, 2020)

Fabrication of Nanosuspensions to Improve the Oral Bioavailability of Total Flavones from Hippophae rhamnoides L. and their Comparison with an Inclusion Complex - Rui Tian; Hui Wang; Yi Xiao; Pengyue Hu; Ruofei Du; Xiufeng Shi; Zhengtao Wang; Yan Xie (AAPS PharmSciTech, 2020)

The abscisic acid receptor gene VvPYL4 positively regulates grapevine resistance to Plasmopara viticola - Li Liu; Chang-Yuan Liu; Hui Wang; Shu-Yi Yu; Tian-Shu Guan; Yu-Fei Huang; Rui-Chun Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Ablation of olfactory bulb glutamatergic neurons induces depressive-like behaviors and sleep disturbances in mice - Mao-Yun Yuan; Ze-Ka Chen; Jian Ni; Tian-Xiao Wang; Shi-Yu Jiang; Hui Dong; Wei-Min Qu; Zhi-Li Huang; Rui-Xi Li (Psychopharmacology, 2020)

Prefrontal Nectin3 Reduction Mediates Adolescent Stress-Induced Deficits of Social Memory, Spatial Working Memory, and Dendritic Structure in Mice - Hong-Li Wang; Ji-Tao Li; Han Wang; Ya-Xin Sun; Rui Liu; Xiao-Dong Wang; Yun-Ai Su; Tian-Mei Si (Neuroscience Bulletin, 2020)
Chronic stress may disrupt the normal neurodevelopmental trajectory of the adolescent brain (especially the prefrontal cortex) and contribute to the pathophysiology of stress-related mental illnesses, but the underlying molecular mechanisms remain unclear. Here, we investigated how synaptic cell adhesion molecules (e.g., nectin3) are involved in the effects of adolescent chronic stress on mouse medial prefrontal cortex (mPFC). Male C57BL/6N mice were subjected to chronic social instability stress from postnatal days 29 to 77. One week later, the mice exposed to chronic stress exhibited impaired social recognition and spatial working memory, simplified dendritic structure, and reduced spine density in the mPFC. Membrane localization of nectin3 was also altered, and was significantly correlated with behavioral performance. Furthermore, knocking down mPFC nectin3 expression by adeno-associated virus in adolescent mice reproduced the stress-induced changes in behavior and mPFC morphology. These results support the hypothesis that nectin3 is a potential mediator of the effects of adolescent chronic stress on prefrontal structural and functional abnormalities.

Critical transition of soil bacterial diversity and composition triggered by nitrogen enrichment - Weixing Liu; Lin Jiang; Sen Yang; Zhou Wang; Rui Tian; Ziyang Peng; Yongliang Chen; Xingxu Zhang; Jialiang Kuang; Ning Ling; Shaopeng Wang; Lingli Liu (Ecology, 2020)
Soil bacterial communities are pivotal in regulating terrestrial biogeochemical cycles and ecosystem functions. The increase in global nitrogen (N) deposition has impacted various aspects of terrestrial ecosystems, but we still have a rudimentary understanding of whether there is a threshold for N input level beyond which soil bacterial communities will experience critical transitions. Using high‐throughput sequencing of the 16S rRNA gene, we examined soil bacterial responses to a long‐term (13 yr), multi‐level, N addition experiment in a temperate steppe of northern China. We found that plant diversity decreased in a linear fashion with increasing N addition. However, bacterial diversity responded nonlinearly to N addition, such that it was unaffected by N input below 16 g N·m −2 ·yr −1 , but decreased substantially when N input exceeded 32 g N·m −2 ·yr −1 . A meta‐analysis across four N addition experiments in the same study region further confirmed this nonlinear response of bacterial diversity to N inputs. Substantial changes in soil bacterial community structure also occurred between N input levels of 16 to 32 g N·m −2 ·yr −1 . Further analysis revealed that the loss of soil bacterial diversity was primarily attributed to the reduction in soil pH, whereas changes in soil bacterial community were driven by the combination of increased N availability, reduced soil pH, and changes in plant community structure. In addition, we found that N addition shifted bacterial communities toward more putatively copiotrophic taxa. Overall, our study identified a threshold of N input level for bacterial diversity and community composition. The nonlinear response of bacterial diversity to N input observed in our study indicates that although bacterial communities are resistant to low levels of N input, further increase in N input could trigger a critical transition, shifting bacterial communities to a low‐diversity state.

Assessment of genetic diversity in Camellia oleifera Abel. accessions using inter-simple sequence repeat (ISSR) and start codon targeted (SCoT) polymorphic markers - Pu Xiao; Huhu Liu; Dongping Wang; Wenyan Tang; Hui Yang; Chong Wang; Zhilong He; Rui Wang; Xiangnan Wang; Xiangyang Lu; Yongzhong Chen; Yun Tian (Genetic Resources and Crop Evolution, 2020)

The stability and pressure behavior characteristics of a special L-type face end formed by low-pressure mining technology without pre-driving roadway - Ya-jun Wang; Jun Yang; Man-chao He; Rui-feng Huang; Xi-chun Tian; Jian-ning Liu; Hao-jie Xue (Arabian Journal of Geosciences, 2020)

TNF-α suppresses sweat gland differentiation of MSCs by reducing FTO-mediated m6A-demethylation of Nanog mRNA - Yihui Wang; Rui Wang; Bin Yao; Tian Hu; Zhao Li; Yufan Liu; Xiaoli Cui; Liuhanghang Cheng; Wei Song; Sha Huang; Xiaobing Fu (Science China Life Sciences, 2020)

Preparation and In vitro Evaluation of FDM 3D-Printed Ellipsoid-Shaped Gastric Floating Tablets with Low Infill Percentages - Di Chen; Xiang-Yu Xu; Rui Li; Gen-Ao Zang; Yue Zhang; Ming-Rui Wang; Meng-Fei Xiong; Jia-Rui Xu; Ting Wang; Hui Fu; Qin Hu; Bin Wu; et al. (AAPS PharmSciTech, 2020)

Urinary bisphenol A (BPA) concentrations and exposure predictors among pregnant women in the Laizhou Wan Birth Cohort (LWBC), China - Shasha Zhao; Caifeng Wang; Rui Pan; Rong Shi; Weiye Wang; Ying Tian (Environmental Science and Pollution Research, 2019)

Enhanced water solubility, antioxidant activity, and oral absorption of hesperetin by D-α-tocopheryl polyethylene glycol 1000 succinate and phosphatidylcholine - Su-Fang Gu; Li-Ying Wang; Ying-Jie Tian; Zhu-Xian Zhou; Jian-Bin Tang; Xiang-Rui Liu; Hai-Ping Jiang; You-Qing Shen (Journal of Zhejiang University-SCIENCE B, 2019)

Alzheimer’s Disease Risk Variant rs2373115 Regulates GAB2 and NARS2 Expression in Human Brain Tissues - Guiyou Liu; Tao Wang; Rui Tian; Yang Hu; Zhifa Han; Pingping Wang; Wenyang Zhou; Peng Ren; Jian Zong; Shuilin Jin; Qinghua Jiang (Journal of Molecular Neuroscience, 2018)

SNAI1, an endothelial–mesenchymal transition transcription factor, promotes the early phase of ocular neovascularization - Jia-Xing Sun; Tian-Fang Chang; Man-Hong Li; Li-Juan Sun; Xian-Chun Yan; Zi-Yan Yang; Yuan Liu; Wen-Qin Xu; Yang Lv; Jing-Bo Su; Liang Liang; Hua Han; et al. (Angiogenesis, 2018)

Ancylomarina psychrotolerans sp. nov., isolated from sediments of Fildes Peninsula and emended the description of genus Ancylomarina - Chao Jia; Hong-chang Cui; Yan-qiong Han; Tian-yu Fu; Rui Du; Xiao-lei Wang; Xiao-chong Shi; Xiao-Hua Zhang (Antonie van Leeuwenhoek, 2018)

Overexpression of Nogo receptor 3 (NgR3) correlates with poor prognosis and contributes to the migration of epithelial cells of nasopharyngeal carcinoma patients - Jiang-Yi He; Ping Han; Yu Zhang; Yong-Dong Liu; Shi-Jian Song; Guo-Kai Feng; Yu An; Ai-Jun Zhou; Hong-Bo Wang; Li Yuan; Zhi-Rui Lin; Tian-Liang Xia; et al. (Journal of Molecular Medicine, 2018)

Response of soil physical and chemical properties to Rocky desertification succession in South China Karst - Maoyin Sheng; Kangning Xiong; Linjiao Wang; Xiaona Li; Rui Li; Xingjun Tian (Carbonates and Evaporites, 2018)

Microsatellite records for volume 10, issue 1 - Ai-Qing Yu; Chengxin Fu; Chongbo He; Fei Liu; Guo-Hua Ding; Hongman Hou; Jian Zhao; Jianmin Yang; Jiansheng Wang; Kun-ci Chen; Lan-lan Zhang; Pan Li; et al. (Conservation Genetics Resources, 2018)

Three new polyketides from the marine sponge-derived fungus Trichoderma sp. SCSIO41004 - Xiaoyan Pang; Xiuping Lin; Yongqi Tian; Rui Liang; Junfeng Wang; Bin Yang; Xuefeng Zhou; Kumaravel Kaliyaperumal; Xiaowei Luo; Zhengchao Tu; Yonghong Liu (Natural Product Research, 2018)

Spatiotemporal Variability of Contaminants in Lake Water and Their Risks to Human Health: A Case Study of the Shahu Lake Tourist Area, Northwest China - Peiyue Li; Wei Feng; Chenyang Xue; Rui Tian; Siting Wang (Exposure and Health, 2017)

Molecular Mechanisms of Vascular Dementia: What Can Be Learned from Animal Models of Chronic Cerebral Hypoperfusion? - Si-Qi Du; Xue-Rui Wang; Ling-Yong Xiao; Jian-Feng Tu; Wen Zhu; Tian He; Cun-Zhi Liu (Molecular Neurobiology, 2017)

Remains of trilobites and other species discovered in a volcanic ash bed of the end-Permian, Yangtze craton, South China - Zejin Shi; Leixun Lu; Guan Yin; Hongyu Long; Wenjie Li; Huaixin Yang; Rui Cao; Xuesong Tian; Qian Tan; Kun Wang; Yong Wang; Yaming Tian (International Geology Review, 2017)

A new C 20 -diterpenoid alkaloid from the lateral roots of Aconitum carmichaeli - Jing Yu; Tian-Peng Yin; Jia-Peng Wang; Rui-Feng Mei; Le Cai; Zhong-Tao Ding (Natural Product Research, 2017)

Nurr1 promotes intestinal regeneration after ischemia/reperfusion injury by inhibiting the expression of p21 (Waf1/Cip1) - Guo Zu; Jihong Yao; Anlong Ji; Shili Ning; Fuwen Luo; Zhenlu Li; Dongcheng Feng; Yiqi Rui; Yang Li; Guangzhi Wang; Xiaofeng Tian (Journal of Molecular Medicine, 2017)

Early postnatal stress suppresses the developmental trajectory of hippocampal pyramidal neurons: the role of CRHR1 - Rui Liu; Xiao-Dun Yang; Xue-Mei Liao; Xiao-Meng Xie; Yun-Ai Su; Ji-Tao Li; Xiao-Dong Wang; Tian-Mei Si (Brain Structure and Function, 2016)

Functional analysis of a chitinase gene during the larval-nymph transition in Panonychus citri by RNA interference - Wen-Kai Xia; Xiao-Min Shen; Tian-Bo Ding; Jin-Zhi Niu; Rui Zhong; Chong-Yu Liao; Ying-Cai Feng; Wei Dou; Jin-Jun Wang (Experimental and Applied Acarology, 2016)

Curdlan blocks the immune suppression by myeloid-derived suppressor cells and reduces tumor burden - Ke Rui; Jie Tian; Xinyi Tang; Jie Ma; Ping Xu; Xinyu Tian; Yungang Wang; Huaxi Xu; Liwei Lu; Shengjun Wang (Immunologic Research, 2016)

Identification of a Novel Rat NR2B Subunit Gene Promoter Region Variant and Its Association with Microwave-Induced Neuron Impairment - Li-Feng Wang; Da-Wei Tian; Hai-Juan Li; Ya-Bing Gao; Chang-Zhen Wang; Li Zhao; Hong-Yan Zuo; Ji Dong; Si-Mo Qiao; Yong Zou; Lu Xiong; Hong-Mei Zhou; et al. (Molecular Neurobiology, 2016)

Upregulation of long noncoding RNA TMEVPG1 enhances T helper type 1 cell response in patients with Sjögren syndrome - Juan Wang; Huiyong Peng; Jie Tian; Jie Ma; Xinyi Tang; Ke Rui; Xinyu Tian; Yungang Wang; Jianguo Chen; Liwei Lu; Huaxi Xu; Shengjun Wang (Immunologic Research, 2016)

α7nAChR is expressed in satellite cells at different myogenic status during skeletal muscle wound healing in rats - Zhi-Ling Tian; Shu-Kun Jiang; Miao Zhang; Meng Wang; Jiao-Yong Li; Rui Zhao; Lin-Lin Wang; Min Liu; Shan-Shan Li; Meng-Zhou Zhang; Da-Wei Guan (Journal of Molecular Histology, 2015)

Antimicrobial activity of human β-defensins against lactic acid bacteria - Xiao-Fang Wang; Fei Tian; Rui-Ming Cao; Jing Li; Sheng-Mei Wu; Xiao-Kui Guo; Tong-Xin Chen (Natural Product Research, 2015)

Decreased expression of microRNA-125a-3p upregulates interleukin-23 receptor in patients with Hashimoto’s thyroiditis - Huiyong Peng; Yingzhao Liu; Jie Tian; Jie Ma; Xinyi Tang; Jun Yang; Ke Rui; Yue Zhang; Chaoming Mao; Liwei Lu; Huaxi Xu; Shengjun Wang (Immunologic Research, 2015)

Review and evaluation of China’s standards and regulations on the fuel consumption of motor vehicles - Yue-Fu Jin; Zhao Wang; Hui-Ming Gong; Tian-Lei Zheng; Xiang Bao; Jia-Rui Fan; Michael Wang; Miao Guo (Mitigation and Adaptation Strategies for Global Change, 2015)

GITRL as a genetic adjuvant enhances enterovirus 71 VP1 DNA vaccine immunogenicity - Jing Yuan; Xinyi Tang; Kai Yin; Jie Tian; Ke Rui; Jie Ma; Chaoming Mao; Jianguo Chen; Liwei Lu; Huaxi Xu; Shengjun Wang (Immunologic Research, 2015)

A poplar R2R3-MYB transcription factor, PtrMYB152, is involved in regulation of lignin biosynthesis during secondary cell wall formation - Chaofeng Li; Xianqiang Wang; Wanxiang Lu; Rui Liu; Qiaoyan Tian; Yiming Sun; Keming Luo (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Investigation on Etiology of Hepatic Venous Obstruction Budd-Chiari Syndrome - Zhi-Long Tian; Gao-Lei Jia; Hai-Lin Xi; Su Feng; Xiao-Kai Wang; Rui Li (Cell Biochemistry and Biophysics, 2014)

An overview of passive and active dust detection methods using satellite measurements - Bin Chen; Peng Zhang; Beidou Zhang; Rui Jia; Zhijuan Zhang; Tianhe Wang; Tian Zhou (Journal of Meteorological Research, 2014)

Semicarbazide – from state-of-the-art analytical methods and exposure to toxicity: a review - Wen-Rui Tian; Ya-Xin Sang; Xiang-Hong Wang (Food Additives & Contaminants: Part A, 2014)

Distance effect of matrix attachment regions on transgene expression in stably transfected Chinese hamster ovary cells - Jun-He Zhang; Xiao-Yin Wang; Tian-Yun Wang; Fang Wang; Wei-Hua Dong; Li Wang; Chun-Peng Zhao; Shu-Jie Chai; Rui Yang; Qin Li (Biotechnology Letters, 2014)

Modeling Carbon Fluxes Using Multi-Temporal MODIS Imagery and CO2 Eddy Flux Tower Data in Zoige Alpine Wetland, South-West China - Xiaoming Kang; Yanfen Wang; Huai Chen; Jianqing Tian; Xiaoyong Cui; Yichao Rui; Lei Zhong; Paul Kardol; Yanbin Hao; Xiangming Xiao (Wetlands, 2014)

Detection of respiratory syncytial virus fusion protein variants between 2009 and 2012 in China - Qiuling Xia; Lili Zhou; Caijing Peng; Rui Hao; Ke Ni; Na Zang; Luo Ren; Yu Deng; Xiaohong Xie; Linli He; Daiyin Tian; Lijia Wang; et al. (Archives of Virology, 2014)

Markers associated with altitude and ecological factors in hexaploid Campeiostachys nutans (Griseb.) J. L. Yang, B. R. Baum et C. Yen and tetraploid Roegeneria nutans (Keng) Keng - Yu-Xia Guo; Cheng-Zhang Wang; Xue-Bing Yan; Rui-Yong Wang; Sha-Sha Liu; Miao Tian (Genetic Resources and Crop Evolution, 2014)

Preparation and Characteristics of Sugarcane Low Alcoholic Drink by Submerged Alcoholic Fermentation - Gan-Lin Chen; Feng-Jin Zheng; Bo Lin; Tian-Shun Wang; Yang-Rui Li (Sugar Tech, 2013)

Screening and test of CD40 related signal transduction pathway in AGS cells and construction of gene silencing vector - Rui Li; Wei-Chang Chen; Xue-Qin Pang; Wen-Yan Tian; Wei-Peng Wang; Xue-Guang Zhang (Molecular Biology Reports, 2013)

Involvement of dopamine D2 receptors activation in ischemic post-conditioning-induced cardioprotection through promoting PKC-ε particulate translocation in isolated rat hearts - Jun Gao; Jin Guo; Hongxia Li; Shuzhi Bai; Hong Li; Bo Wu; Lina Wang; Yuhui Xi; Ye Tian; Guangdong Yang; Rui Wang; Lingyun Wu; et al. (Molecular and Cellular Biochemistry, 2013)

Effects of grazing on CO2 balance in a semiarid steppe: field observations and modeling - Xiaoming Kang; Yanbin Hao; Xiaoyong Cui; Huai Chen; Changsheng Li; Yichao Rui; Jianqing Tian; Paul Kardol; Lei Zhong; Jinzhi Wang; Yanfen Wang (Journal of Soils and Sediments, 2013)

Effect of PI3K gene silencing on growth, migration and related proteins expression of CD40 signal-mediated gastric cancer cells - Rui Li; Wei-Chang Chen; Xue-Qin Pang; Wen-Yan Tian; Wei-Peng Wang; Xue Guang Zhang (Molecular Biology Reports, 2013)

Combined effect of sCD40L and PI3K siRNA on transplanted tumours growth and microenvironment in nude mice with gastric cancer - Rui Li; Wei-Chang Chen; Xue-Qin Pang; Wen-Yan Tian; Wei-Peng Wang; Xue-Guang Zhang (Molecular Biology Reports, 2012)

CD40 signal expression in gastric cancer tissue and its correlation with prognosis of gastric cancer patients - Rui Li; Wei-Chang Chen; Xue-Qin Pang; Wen-Yan Tian; Wei-Peng Wang; Xue Guang Zhang (Molecular Biology Reports, 2012)

Involvement of calcium-sensing receptor in oxLDL-induced MMP-2 production in vascular smooth muscle cells via PI3K/Akt pathway - Hong-Xia Li; Fan-Juan Kong; Shu-Zhi Bai; Wen He; Wen-Jing Xing; Yu-Hui Xi; Guang-Wei Li; Jin Guo; Hong-Zhu Li; Ling-Yun Wu; Rui Wang; Guang-Dong Yang; et al. (Molecular and Cellular Biochemistry, 2012)

Molecular and serological diversity in Apple chlorotic leaf spot virus from sand pear (Pyrus pyrifolia) in China - Yansu Song; Ni Hong; Liping Wang; Hongju Hu; Rui Tian; Wenxing Xu; Fang Ding; Guoping Wang (European Journal of Plant Pathology, 2011)

Nicotinic acetylcholine receptor alpha7 subunit is time-dependently expressed in distinct cell types during skin wound healing in mice - Yan-Yan Fan; Tian-Shui Yu; Tao Wang; Wei-Wei Liu; Rui Zhao; Shu-Tao Zhang; Wen-Xiang Ma; Ji-Long Zheng; Da-Wei Guan (Histochemistry and Cell Biology, 2011)

Human Prion Protein Mutants with Deleted and Inserted Octarepeats Undergo Different Pathways to Trigger Cell Apoptosis - Kun Xu; Xin Wang; Qi Shi; Cao Chen; Chan Tian; Xiao-Li Li; Rui-Min Zhou; Yong-Lie Chu; Xiao-Ping Dong (Journal of Molecular Neuroscience, 2011)

Evaluation of Genetic Manipulation Strategies on d-Lactate Production by Escherichia coli - Li Zhou; Zhi-Rui Zuo; Xian-Zhong Chen; Dan-Dan Niu; Kang-Ming Tian; Bernard A. Prior; Wei Shen; Gui-Yang Shi; Suren Singh; Zheng-Xiang Wang (Current Microbiology, 2011)

Extraction of essential oils from garlic (Allium sativum) using ligarine as solvent and its immunity activity in gastric cancer rat - Rui Li; Wei-chang Chen; Wei-peng Wang; Wen-yan Tian; Xue-guang Zhang (Medicinal Chemistry Research, 2010)

Analysis of the essential oil of magnolia and its effect on antioxidant enzyme activity, sCD40L and phosphorylate-activate Akt protein levels in gastric cancer mice - Rui Li; Wei-chang Chen; Wei-peng Wang; Wen-yan Tian; Xue-guang Zhang (Medicinal Chemistry Research, 2010)

Synthesis and biological evaluation of cyclopenten-1-one Mannich base oxovanadium compound - Juan Tian; Dongliu Li; Fengying Zhai; Xiaohong Wang; Rui Li (Medicinal Chemistry Research, 2010)

Responses of Mikania micrantha, an Invasive Weed to Elevated CO2: Induction of β-Caryophyllene Synthase, Changes in Emission Capability and Allelopathic Potential of β-Caryophyllene - Rui-Long Wang; Christian Staehelin; Shao-Lin Peng; Wen-Tian Wang; Xi-Mei Xie; Hui-Ning Lu (Journal of Chemical Ecology, 2010)

Activation of TRPA1 channels by fenamate nonsteroidal anti-inflammatory drugs - Hongzhen Hu; Jinbin Tian; Yingmin Zhu; Chunbo Wang; Rui Xiao; Jeffrey M. Herz; Jackie D. Wood; Michael X. Zhu (Pflügers Archiv - European Journal of Physiology, 2010)

Microbial community structure and diversity in a native forest wood-decomposed hollow-stump ecosystem - Bao-Yu Tian; Qin-Geng Huang; Yan Xu; Chun-Xiang Wang; Rui-Rui Lv; Jian-Zhong Huang (World Journal of Microbiology and Biotechnology, 2010)

Involvement of the ornithine decarboxylase/polyamine system in precondition-induced cardioprotection through an interaction with PKC in rat hearts - Ya-Jun Zhao; Wei-Hua Zhang; Chang-Qing Xu; Hong-Zhu Li; Li-Na Wang; Hong Li; Yi-Hua Sun; Yan Lin; Li-Ping Han; Li Zhang; Yie Tian; Rui Wang; et al. (Molecular and Cellular Biochemistry, 2009)

Manganese-induced changes of the biochemical characteristics of the recombinant wild-type and mutant PrPs - Xiao-Li Li; Chen-Fang Dong; Gui-Rong Wang; Rui-Min Zhou; Qi Shi; Chan Tian; Chen Gao; Guo-Yong Mei; Cao Chen; Kun Xu; Jun Han; Xiao-Ping Dong (Medical Microbiology and Immunology, 2009)

Reduced expression of GSTM2 and increased oxidative stress in spontaneously hypertensive rat - Si-Gui Zhou; Ping Wang; Rong-Biao Pi; Jie Gao; Jia-Jia Fu; Jian Fang; Jia Qin; Hui-Jie Zhang; Rui-Fang Li; Shao-Rui Chen; Fu-Tian Tang; Pei-Qing Liu (Molecular and Cellular Biochemistry, 2008)

FoxO4 is the main forkhead transcriptional factor localized in the gastrointestinal tracts of pigs - Zhen-qi Zhou; Tian Wang; Ling-mei Pan; Rui-hua Huang; Fang-xiong Shi (Journal of Zhejiang University-SCIENCE B, 2007)

The impact of cropland conversion on environmental effect in the Loess Plateau: a pilot study based on the national experimental bases - Wang Fei; Li Rui; Jiao Feng; Yang Qingke; Tian Junliang (Journal of Geographical Sciences, 2005)